Transparent glass-ceramics, substrate glass, chemically strengthened glass-ceramics and their applications
By using lithium feldspar and lithium disilicate crystal phases in microcrystalline glass and adjusting the oxide content and heat treatment process, the optical and strength problems of large-sized microcrystalline glass bricks are solved, and efficient industrial production and excellent performance are achieved .
Patent Information
- Application Number
- CN202311800621.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-25
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2043-12-25
AI Technical Summary
In the production of large-size microcrystalline glass bricks, the problems of uneven optical performance, heat treatment cracking and insufficient strength performance are prone to occur, which is difficult to meet the application requirements of display covers.
Use a specific composition of transparent microcrystalline glass, which contains lithium feldspar crystal phase and lithium disilicate crystal phase, and through adjustment of oxide content relationship and heat treatment process, ensure that the glass brick does not crack during the preparation process and is cold-worked and chemically After the strengthening treatment, excellent optical and mechanical properties are achieved.
Mass production of large-size transparent microcrystalline glass is realized, ensuring uniform optical performance and high strength performance, meeting the application requirements of display covers, and improving the industrial mass production efficiency of the product.
Smart Images

Figure CN117776535B_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the field of microcrystalline glass technology, and specifically relates to a transparent microcrystalline glass, a substrate glass, a chemically strengthened microcrystalline glass and applications thereof. Background Art
[0002] With the development of electronic display technology, glass has gradually replaced plastic materials and is used in display devices as a protective cover material. There are two main types of cover glass for electronic product protection on the market: one is chemically strengthened glass made with ordinary aluminosilicate glass as the substrate, and the other is chemically strengthened microcrystalline glass made by chemically strengthening microcrystalline glass containing microcrystalline phase and glass phase. Among them, microcrystalline glass contains a large number of nano-scale crystals, which can hinder the expansion of microcracks, and its overall strength performance is significantly improved compared with ordinary aluminosilicate glass.
[0003] As microcrystalline glass has better strength than ordinary glass, it has gradually attracted the attention of the industry. However, for microcrystalline glass used in display screens with high requirements for optical display effects and strength performance, it is difficult to produce large-scale microcrystalline glass, and it is difficult to ensure the uniformity of composition and temperature field, which is prone to local optical unevenness or cracking of glass bricks.
[0004] It should be noted that this part of the present application only provides background technology related to the present application and does not necessarily constitute prior art or known technology. Summary of the invention
[0005] In order to improve productivity, when mass-producing microcrystalline glass, the production line usually melts large-sized substrate glass bricks first, then heat-treats the large-sized substrate glass bricks to prepare large-sized microcrystalline glass bricks, and then cold-processes the large-sized microcrystalline glass bricks to obtain multiple microcrystalline glass sheets of the required size specifications.
[0006] However, the existing microcrystalline glass solutions whose main crystal phases are petalite crystal phase and lithium disilicate crystal phase are prone to problems such as poor optical performance of microcrystalline glass bricks and easy cracking of microcrystalline glass bricks when they are put into mass production lines to produce large-sized microcrystalline glass bricks, such as microcrystalline glass bricks with length, width and thickness specifications of (200mm-500mm)×(100mm-500mm)×(10mm-40mm). Among them, the poor optical performance of microcrystalline glass bricks is mainly manifested in that the b-values of different areas of the whole brick vary greatly, and the local area presents an unexpected color, which causes the overall display effect of the microcrystalline glass to fail to meet the application requirements of the display cover, and then leads to a decrease in the product qualification rate. The cracking of microcrystalline glass bricks will directly reduce the output yield, which is not conducive to the mass production of microcrystalline glass products. Products that meet the optical performance requirements are prone to poor strength performance, especially poor drop resistance, which makes it difficult to meet the strength requirements of use.
[0007] The purpose of this application is to overcome the defects of uneven optical properties of the whole brick, cracking due to heat treatment, and inability to balance strength that are prone to occur in the mass production of microcrystalline glass (especially mass production of large-sized microcrystalline glass bricks) in the prior art, and to provide a transparent microcrystalline glass, substrate glass, chemically strengthened microcrystalline glass and their applications.
[0008] The solution provided in the present application is suitable for mass production of large-sized transparent microcrystalline glass bricks that meet the requirements of the cover plate and whose main crystal phases are petalite crystal phases and lithium disilicate crystal phases. During the preparation process of the large-sized transparent microcrystalline glass bricks, that is, when the large-sized substrate glass bricks are heat-treated to prepare transparent microcrystalline glass bricks, there is no cracking of the glass bricks, and the optical properties of the obtained transparent microcrystalline glass bricks are excellent and uniform. Afterwards, the obtained transparent microcrystalline glass bricks are subjected to cold processing (including cutting, CNC, polishing, etc., to obtain the required size specifications) and chemical strengthening treatment, and transparent chemically strengthened microcrystalline glass products that meet the requirements of optical properties, strength properties and display effects can be obtained. The solution provided in the present application improves the production yield and economic benefits of transparent microcrystalline glass whose main crystal phases are petalite crystal phases and lithium disilicate crystal phases, and it is easy to realize the industrial mass production of the transparent microcrystalline glass products.
[0009] In order to achieve the above objectives, this application provides the following technical solutions:
[0010] 1. A transparent glass-ceramic, wherein the transparent glass-ceramic contains a petalite crystalline phase and a lithium disilicate crystalline phase, wherein the petalite crystalline phase and the lithium disilicate crystalline phase have a higher weight percentage than other crystalline phases present in the transparent glass-ceramic;
[0011] Measured in terms of molar percentage of oxides, the composition of the transparent glass-ceramics includes:
[0012] SiO2: 60.90mol%-72.65mol%, Al2O3: 1.50mol%-5.00mol%, P2O5: 0.85mol%-1.50mol%, ZrO2: 2.00mol%-4.00mol%, Na2O: 0.00m ol%-1.00mol%, K2O: 0.00mol%-0.50mol%, Li2O: 20.00mol%-30.00mol%, CaO: 0.00mol%-1.60mol%, B2O3: 0.00mol%-1.00mol%;
[0013] The composition of the transparent glass-ceramics satisfies the following requirements, measured by the content of each oxide in the transparent glass-ceramics as expressed by molar percentage:
[0014] 18.200≤Li2O / P2O5≤25.500;
[0015] 14.000≤2×Li2O / (0.5×ZrO2+CaO)≤23.000. The oxide content and the specific oxide content relationship under the specific conditions satisfied by the technical solution of the present application can not only ensure the formation of the main crystalline phases of petalite and lithium disilicate, but also can avoid the problem of overall bluish, foggy and even cracking of microcrystalline glass bricks when preparing microcrystalline glass bricks from large-sized substrate glass bricks while ensuring the good melting condition of the substrate glass bricks, which is conducive to the transparent microcrystalline glass to obtain excellent optical properties and strength, and thus the overall display effect of the transparent microcrystalline glass can meet the application requirements of the display cover. At the same time, the transparent microcrystalline glass of the present application can obtain high-strength chemically strengthened microcrystalline glass after chemical strengthening treatment.
[0016] 2. The transparent microcrystalline glass as described in technical solution 1, wherein the composition of the transparent microcrystalline glass satisfies the following conditions, expressed in terms of the molar percentage of each oxide in the composition of the transparent microcrystalline glass:
[0017] 4.100≤(Li2O+Na2O+K2O+B2O3) / (P2O5+ZrO2+CaO)≤6.000; and / or,
[0018] 0.100≤P2O5×(CaO+ZrO2+Li2O+Al2O3) / (Na2O+K2O+B2O3)≤0.900, preferably, 0.190≤P2O5×(CaO+ZrO2+Li2O+Al2O3) / (Na2O+K2O+B2O3)≤0.900. By making the composition satisfy at least one of the above relationship, it is beneficial to further improve the network structure and crystal phase structure of the transparent microcrystalline glass, thereby facilitating the formation of a transparent microcrystalline glass that meets a specific structure and has excellent performance (especially optical performance, strength performance, etc.).
[0019] It should be pointed out that in the above formulas of the present application, the content percentage is substituted into each formula on a molar basis, that is, the molar unit does not participate in the calculation of the formula. For example, if the molar content of P2O5 is 0.85%, 0.85% is substituted into the formula for calculation.
[0020] 3. The transparent glass-ceramics according to technical solution 1 or 2, wherein, in terms of molar percentage of oxides, the composition of the transparent glass-ceramics comprises:
[0021] SiO2: 67.50mol%-71.00mol%, Al2O3: 3.50mol%-5.00mol%, P2O5: 0.85mol%-1.50mol%, ZrO2: 2.50mol%-3.50mol%, Na2O: 0.00mol%-1.00mol%, K2O: greater than 0.00mol% and not greater than 0.50mol%, Li2O: 20.00mol%-25.00mol%, CaO: greater than 0.50mol% and not greater than 1.60mol%, B2O3: 0.00mol%-1.00mol%. By adjusting the content relationship of the necessary oxides, it is beneficial to further improve the network structure of the transparent microcrystalline glass, thereby ensuring the large-scale mass production effect of the transparent microcrystalline glass and ensuring the excellent optical properties and strength properties of the mass-produced products.
[0022] 4. The transparent glass-ceramic as described in any one of technical solutions 1 to 3, wherein the transparent glass-ceramic does not contain a quartz crystal phase. By avoiding the precipitation of a quartz crystal phase in a transparent glass-ceramic whose main crystal phases are a petalite crystal phase and a lithium disilicate crystal phase, it is helpful to further ensure the optical properties and overall uniformity of the transparent glass-ceramic.
[0023] 5. The transparent microcrystalline glass as described in any one of technical solutions 1 to 4, wherein the crystallinity of the transparent microcrystalline glass is ≥ 70.00wt%, preferably ≥ 80.00wt%; in the transparent microcrystalline glass, the average crystal size does not exceed 100nm. A higher content of microcrystalline phase is conducive to improving the mechanical strength of the microcrystalline glass. A smaller average crystal size is conducive to ensuring the excellent optical properties of the transparent microcrystalline glass.
[0024] 6. The transparent glass-ceramics as described in any one of technical solutions 1 to 5, wherein in the transparent glass-ceramics, the petalite crystal phase accounts for 35.00wt%-50.00wt% of the mass of the transparent glass-ceramics, and the lithium disilicate crystal phase accounts for 35.00wt%-50.00wt% of the mass of the transparent glass-ceramics. By adjusting the petalite crystal phase and the lithium disilicate crystal phase to meet a suitable ratio, it is beneficial to form a specific microstructure, which is beneficial to ensure that the transparent glass-ceramics has high mechanical strength and fracture toughness.
[0025] 7. A transparent microcrystalline glass as described in any one of technical solutions 1 to 6, wherein the transparent microcrystalline glass also contains one or more of a lithium silicate crystal phase, a lithium phosphate crystal phase, and a spodumene crystal phase as a secondary crystalline phase.
[0026] 8. The transparent glass-ceramic as described in technical solution 7, wherein in the transparent glass-ceramic, the secondary crystalline phase accounts for less than 30.00wt% of the mass of the transparent glass-ceramic, and preferably, the secondary crystalline phase accounts for less than 10.00wt% of the mass of the transparent glass-ceramic. By controlling the low content of the secondary crystalline phase, it is more conducive to ensuring the high content of the main crystalline phase, thereby ensuring the excellent mechanical strength performance of the transparent glass-ceramic.
[0027] 9. The transparent microcrystalline glass as described in any one of technical solutions 1 to 8, wherein, when the length, width and thickness specifications of the transparent microcrystalline glass are (200mm-500mm)×(100mm-500mm)×(10mm-40mm), the range of the b value at nine locations on the main surface of the transparent microcrystalline glass is ≤2.00, preferably ≤1.50, and more preferably ≤1.00. The smaller the range of the b value at nine locations on the main surface of the transparent microcrystalline glass that meets this specification, the better the overall uniformity and the better the optical effect of the transparent microcrystalline glass of the present application when it is produced to this specification, which is conducive to ensuring that the microcrystalline glass sheets cut therefrom meet the requirements of excellent optical performance and display effects.
[0028] The nine positions are: (1) four test positions of the test circle I that is tangent to the long side and the adjacent short side on the main surface; (2) four test positions of the test circle II formed by the point on the line segment formed by the centers of the four test circles I that is closest to the middle of the long side or the short side of the main surface; (3) one test circle III formed by the center point of the main surface.
[0029] 10. The transparent microcrystalline glass as described in any one of technical solutions 1 to 8, wherein, when the length, width and thickness specifications of the transparent microcrystalline glass are (45mm-450mm)×(45mm-350mm)×(0.4mm-2.0mm), the range of the b value at nine locations on the main surface of the transparent microcrystalline glass is ≤0.30, preferably ≤0.10, and more preferably ≤0.06. The nine locations are the same as those of technical solution 9. The smaller the range of the b value at nine locations on the main surface of the microcrystalline glass sheet of this specification, the better the overall uniformity of the transparent microcrystalline glass of the present application, and the better the overall display effect.
[0030] 11. A transparent microcrystalline glass as described in any one of technical solutions 1 to 10, wherein, when the thickness of the transparent microcrystalline glass is 0.6 mm, the b value is ≤1.00, preferably the b value is ≤0.70, the haze is ≤0.25%, preferably the haze is ≤0.18%, and under light of a wavelength of 550 nm, the transmittance of the transparent microcrystalline glass is ≥90.00%.
[0031] Preferably, when the thickness of the transparent microcrystalline glass is 0.6 mm, the b value is ≤ 0.60, the haze is ≤ 0.16%, and the transmittance of the transparent microcrystalline glass is ≥ 90.50% under 550 nm wavelength light. The higher the transmittance, the smaller the b value and the haze, the better the optical performance of the transparent microcrystalline glass.
[0032] 12. A substrate glass, which can be used to prepare the transparent microcrystalline glass as described in any one of technical solutions 1 to 11 after heat treatment, wherein the composition of the substrate glass, calculated by molar percentage of oxides, includes:
[0033] SiO2: 60.90mol%-72.65mol%, Al2O3: 1.50mol%-5.00mol%, P2O5: 0.85mol%-1.50mol%, ZrO2: 2.00mol%-4.00mol%, Na2O: 0.00m ol%-1.00mol%, K2O: 0.00mol%-0.50mol%, Li2O: 20.00mol%-30.00mol%, CaO: 0.00mol%-1.60mol%, B2O3: 0.00mol%-1.00mol%;
[0034] The composition of the substrate glass satisfies the following conditions, expressed in terms of the molar percentage of each oxide in the substrate glass composition:
[0035] 18.200≤Li2O / P2O5≤25.500;
[0036] 14.000≤2×Li2O / (0.5×ZrO2+CaO)≤23.000. By making the substrate glass meet the above composition requirements, not only can the substrate glass bricks be ensured to achieve good melting conditions, but also transparent microcrystalline glass bricks with good overall uniformity, good display effect, excellent optical properties, excellent mechanical properties, and main crystal phases of petalite crystal phase and lithium disilicate crystal phase can be prepared, which is beneficial to improve the mass production yield of the transparent microcrystalline glass of the system.
[0037] 13. The substrate glass according to technical solution 12, wherein the composition of the substrate glass satisfies the following conditions, expressed in terms of the molar percentage of each oxide in the substrate glass composition:
[0038] 4.100≤(Li2O+Na2O+K2O+B2O3) / (P2O5+ZrO2+CaO)≤6.000; and / or,
[0039] 0.100≤P2O5×(CaO+ZrO2+Li2O+Al2O3) / (Na2O+K2O+B2O3)≤0.900, preferably 0.190≤P2O5×(CaO+ZrO2+Li2O+Al2O3) / (Na2O+K2O+B2O3)≤0.900. By making the composition satisfy at least one of the above relationship, it is beneficial to further improve the network structure of the glass, thereby facilitating the preparation of transparent microcrystalline glass that meets the specific structure and has excellent performance (especially optical performance, strength performance, etc.).
[0040] 14. The substrate glass as described in technical solution 12 or 13, wherein, after synchronous thermal analysis testing, under a nitrogen protective atmosphere, the substrate glass is heated from room temperature to 900°C at a heating rate of 10°C / min to obtain a heating DSC curve, in which there are at least two exothermic peaks, wherein the first exothermic peak temperature T1 is 600°C-730°C, and the second exothermic peak temperature T2 is 740°C-800°C, and T1 and T2 satisfy the relationship: 100°C ≥ T2-T1 ≥ 40°C, preferably 80°C ≥ T2-T1 ≥ 50°C. Large-size substrate glass bricks made of substrate glass that meets specific DSC curve characteristics are heat-treated under the production line process conditions for mass production of microcrystalline glass to produce transparent microcrystalline glass bricks whose optical properties and display effects meet the requirements for display screens. This can effectively solve the problems of glass brick cracking, large differences in b-values in different areas of the glass bricks, localized unexpected colors, spots, poor display, and other problems that are prone to occur in mass production of microcrystalline glass bricks in the prior art.
[0041] 15. The substrate glass as described in any one of technical solutions 12-14, wherein, after a synchronous thermal analysis test, the substrate glass is heated from room temperature to 1400°C at a heating rate of 10°C / min and kept at that temperature for 10 minutes under a nitrogen atmosphere, and then cooled from 1400°C to 450°C at a cooling rate of 10°C / min, to obtain a cooling DSC curve, in which, within the range of 500°C-900°C, the sum of the integral areas of the exothermic peaks and endothermic peaks contained therein is S≤10, preferably there is no endothermic peak and / or exothermic peak, and more preferably S=0. Large-sized substrate glass bricks made of substrate glass solutions that meet the characteristics of a specific DSC curve are heat-treated under the production line process conditions for mass production of microcrystalline glass, and transparent microcrystalline glass bricks with optical properties and display effects that meet the requirements for display screens can be obtained, which can well solve the problems of glass brick cracking, large differences in b values in different regions of glass bricks, localized undesirable colors, flower pieces, poor display, etc. that are easy to occur in the mass production of microcrystalline glass bricks in the prior art.
[0042] 16. The substrate glass according to any one of technical solutions 12 to 15, wherein the substrate glass is heated from room temperature to T at a heating rate of 10°C / min. 1-30 temperature, and keep the temperature at this point for 240 minutes for treatment, and the content of quartz crystal phase in the product obtained after treatment is less than 15wt%; wherein, T 1-30 =T1-30℃.
[0043] 17. The substrate glass according to any one of technical solutions 12 to 16, wherein the substrate glass is heated from room temperature to T at a heating rate of 10°C / min. 1-60 temperature, and keep the temperature at this point for 240 minutes for treatment, wherein the content of quartz crystal phase in the product obtained after treatment is less than 5wt%, preferably no quartz crystal phase; wherein T 1-60 =T1-60℃.
[0044] In T 1-30 and / or T 1-60 The substrate glass that meets the specific quartz crystal phase content requirements after heat treatment at a certain temperature can effectively avoid the precipitation of quartz crystal phases that affect the optical properties of the target microcrystalline glass bricks when the target microcrystalline glass is prepared by heat treatment, thereby ensuring the mass production of large-sized transparent microcrystalline glass bricks that meet the use requirements.
[0045] 18. A chemically strengthened glass-ceramic, wherein the composition at the center of the chemically strengthened glass-ceramic is the same as the composition of the transparent glass-ceramic described in any one of technical solutions 1 to 11, the chemically strengthened glass-ceramic includes a compressive stress layer region extending from the surface of the transparent glass-ceramic to the compression depth, and has tensile stress inside the chemically strengthened glass-ceramic. By forming a compressive stress layer on the surface of the transparent glass-ceramic, the mechanical properties of the transparent glass-ceramic are further improved.
[0046] 19. The chemically strengthened glass-ceramics as described in technical solution 18, wherein the chemically strengthened glass-ceramics is obtained by chemically strengthening the transparent glass-ceramics described in any one of technical solutions 1-11, wherein the salt bath used for chemical strengthening treatment is a mixed molten salt, and the composition of the mixed molten salt includes: 0<NaNO3<100wt%, 0<KNO3<100wt%, 0<LiNO3≤0.2wt%.
[0047] Preferably, the temperature of the chemical strengthening salt bath is 430° C.-530° C., and the chemical strengthening treatment time is 0.5 h-15.0 h. Using the above strengthening process for chemical strengthening is conducive to improving the chemical strengthening efficiency and ensuring that the chemically strengthened glass-ceramics obtains the desired stress level.
[0048] 20. The chemically strengthened glass-ceramics according to claim 18 or 19, wherein the surface Na2O concentration of the chemically strengthened glass-ceramics is 5.0wt%-20.0wt%. By satisfying the surface Na2O concentration within the above range, it is possible to ensure that the chemically strengthened glass-ceramics has a better surface stress level and better weather resistance and chemical durability.
[0049] 21. The chemically strengthened glass-ceramic as described in any one of technical solutions 18 to 20, wherein the chemically strengthened glass-ceramic has a CS_50 of 110-200 MPa, and CS_50 refers to the compressive stress value at a depth of 50 μm from the main surface of the chemically strengthened glass-ceramic. The range of CS_50 of the chemically strengthened glass-ceramic is within the above range, indicating that the compressive stress of the chemically strengthened glass-ceramic at a depth of 50 μm from the surface is high, indicating that the chemically strengthened glass-ceramic has a higher surface stress level, and the higher the surface compressive stress level, the more residual energy of the drop collision can be offset, thereby ensuring that it has excellent damage resistance.
[0050] 22. The chemically strengthened glass-ceramic as described in any one of technical solutions 18 to 21, wherein the chemically strengthened glass-ceramic has a |CT_AV| of 84-140 MPa, where |CT_AV| refers to the absolute value of the average tensile stress. The |CT_AV| of the chemically strengthened glass-ceramic is within the above range, indicating that the chemically strengthened glass-ceramic has a higher tensile stress level, reflecting that it has a higher surface stress level, and the higher the surface compressive stress level, the more residual energy of the drop collision can be offset, thereby ensuring that it has excellent damage resistance.
[0051] 23. The chemically strengthened glass-ceramic as described in any one of technical solutions 18 to 22, wherein the compressive stress layer depth DOL_0 of the chemically strengthened glass-ceramic is 0.18t-0.25t, and t is the thickness of the chemically strengthened glass-ceramic. The DOL_0 of the chemically strengthened glass-ceramic is within the above range, indicating that the chemically strengthened glass-ceramic has a high compressive stress layer depth, which is more conducive to offsetting the energy driving the crack extension, thereby ensuring that it has excellent damage resistance.
[0052] 24. The chemically strengthened glass-ceramic according to any one of technical solutions 18 to 23, wherein the chemically strengthened glass-ceramic with a thickness of 0.6 mm is subjected to multiple fixed-point height drop tests using 120-grit sandpaper, the fixed-point height of the test is 1.0 m, and the number of times the chemically strengthened glass-ceramic is dropped to break is ≥ 30, preferably ≥ 50. When the fixed-point height is dropped and broken, the more times it is dropped to break, the better the drop damage resistance of the chemically strengthened glass-ceramic is.
[0053] 25. A method for preparing a transparent microcrystalline glass as described in any one of technical solutions 1-11, comprising: heat-treating the substrate glass as described in any one of technical solutions 12-17 to obtain the transparent microcrystalline glass.
[0054] The heat treatment described in the present application includes nucleation treatment and crystallization treatment, wherein the temperature of the nucleation treatment is (Tg-20°C) to (Tg+40°C), the time of the nucleation treatment is 0min-6000min, the temperature of the crystallization treatment is (T1-20°C) to (T1+20°C), and the time of the crystallization treatment is 30min-6000min; Tg is the glass transition temperature of the substrate glass.
[0055] Preferably, the heating rate of the heat treatment process is 5-15°C / min.
[0056] 26. A glass device, wherein the glass device comprises the transparent microcrystalline glass as described in any one of Technical Solutions 1 to 11 or comprises the chemically strengthened microcrystalline glass as described in any one of Technical Solutions 18 to 24.
[0057] 27. An electronic device, wherein the electronic device comprises the transparent microcrystalline glass as described in any one of Technical Solutions 1-11 or comprises the chemically strengthened microcrystalline glass as described in any one of Technical Solutions 18-24.
[0058] One or more of the above technical solutions have the following advantages or beneficial effects:
[0059] The present application optimizes the glass formula and adopts a glass solution that meets specific composition requirements, especially the oxide content under specific conditions and the specific oxide content relationship. This can solve the problem of easy cracking of microcrystalline glass bricks when mass-producing large-sized transparent microcrystalline glass with the main crystal phases being petalite crystal phase and lithium disilicate crystal phase. At the same time, it can ensure that the prepared transparent microcrystalline glass has both excellent optical properties and strength properties, and ensure that its display effect can meet the requirements.
[0060] Among them, the oxide content and the specific oxide content relationship under the specific conditions satisfied by the technical solution of the present application can not only ensure the formation of the main crystalline phases of petalite and lithium disilicate, but also can avoid the problem of overall blueing, fogging and even cracking of the microcrystalline glass bricks when preparing microcrystalline glass bricks from large-sized substrate glass bricks while ensuring the good melting condition of the substrate glass bricks, which is conducive to the transparent microcrystalline glass to obtain excellent optical properties and strength, and thus the overall display effect of the transparent microcrystalline glass can meet the application requirements of the display cover. At the same time, after the transparent microcrystalline glass of the present application is chemically strengthened, a high-strength chemically strengthened microcrystalline glass can be obtained, and it has been verified that the chemically strengthened microcrystalline glass has excellent drop resistance.
[0061] It has been verified that under large size specifications, the range of the b value at nine locations on the main surface of the transparent microcrystalline glass prepared by the technical solution of the present application is ≤2.00; under small size specifications, the range of the b value at nine locations on the main surface of the transparent microcrystalline glass prepared by the technical solution of the present application is ≤0.30, preferably ≤0.10, which shows that regardless of large size or small size, the difference in b value in different areas of the main surface of the transparent microcrystalline glass of the present application is small, the optical performance of the transparent microcrystalline glass is good, and the overall display effect can meet the application requirements of the display cover. Under large size specifications, the microcrystalline glass can meet the uniform b value, which is conducive to ensuring a high product yield.
[0062] Another or more of the above technical solutions have the following advantages or beneficial effects:
[0063] This application adopts a large-sized substrate glass brick made of a specific substrate glass solution that meets the specific DSC curve characteristics. Heat treatment is carried out under the production line process conditions of mass production of microcrystalline glass to produce transparent microcrystalline glass bricks whose optical properties and display effects meet the requirements of display screens. It can well solve the problems of glass brick cracking, large differences in b values in different areas of glass bricks, localized unexpected colors, flowers, poor display, etc. in the prior art during mass production of microcrystalline glass bricks. Therefore, before preparing large-sized microcrystalline glass bricks, glass samples can be melted according to the glass formula, and the DSC curve characteristics obtained can be used to pre-verify whether the glass solution is suitable for the production of large-sized microcrystalline glass, especially qualified microcrystalline glass products with large thickness. If it does not meet the requirements, it can be adjusted in time until it meets the specific DSC curve characteristics before large-sized preparation is carried out, which can greatly save time and cost and effectively avoid waste of resources. BRIEF DESCRIPTION OF THE DRAWINGS
[0064] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work.
[0065] Figure 1 is a DSC curve of the substrate glass of Example 1;
[0066] Figure 2 The DSC curve of the substrate glass of Comparative Example 4 is shown in FIG.
[0067] Figure 3 is a temperature-increasing DSC curve of the substrate glass of Example 1;
[0068] Figure 4 is a temperature-increasing DSC curve of the substrate glass of Example 22;
[0069] Figure 5 The DSC curve of the substrate glass of Comparative Example 1 is as follows;
[0070] Figure 6 The DSC curve of the substrate glass of Comparative Example 2 is as follows;
[0071] Figure 7 The substrate glass of Example 3 is subjected to heat treatment process A (crystallization temperature is T 1-60 , crystallization treatment time is 240min), the XRD diffraction pattern of the obtained product;
[0072] Figure 8 The substrate glass of Comparative Example 2 is subjected to heat treatment process A (crystallization temperature is T1-60 , crystallization treatment time is 240min), the XRD diffraction pattern of the obtained product;
[0073] Fig. 9 The XRD diffraction pattern of the glass-ceramics obtained after the substrate glass of Example 3 is treated by heat treatment process B;
[0074] Fig.10 The XRD diffraction pattern of the glass-ceramics obtained after the substrate glass of Comparative Example 2 is treated by heat treatment process B;
[0075] Fig.11 It is a schematic diagram of the structure of Li3PO4 crystals attached to lithium silicate crystals;
[0076] Fig.12 This is the standard XRD diffraction pattern of quartz in glass-ceramics;
[0077] Fig.13 A schematic diagram of nine test positions when performing b-value tests at nine locations on the main surface of the glass-ceramic. The circles in the figure are all test circle positions;
[0078] Fig.14 This is a schematic diagram of the state of the glass-ceramic petal;
[0079] Fig.15 The XRD diffraction curves of the 0.6 mm thick glass-ceramic sheet of Example 1 at the maximum b value position and the minimum b value position in the nine b value tests are compared;
[0080] Fig.16 The XRD diffraction curves of the 0.6 mm thick microcrystalline glass sheet (with flower pieces) of Comparative Example 6 at the maximum b value position and the minimum b value position in the nine b value tests are compared;
[0081] Fig.17 The transmittance curve of the glass-ceramics obtained after the substrate glass of Example 6 is treated by heat treatment process B when the thickness is 0.6 mm;
[0082] Fig.18 The transmittance curve of the glass-ceramics obtained after the substrate glass of Comparative Example 4 is treated by heat treatment process B with a thickness of 0.6 mm;
[0083] Fig.19 This is a picture of the substrate glass brick of Comparative Example 9;
[0084] Fig. 20 This is a picture of the cracking of the microcrystalline glass brick obtained after the base glass brick in Comparative Example 7 was treated by heat treatment process B. DETAILED DESCRIPTION
[0085] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article. Among them, the terms "optional" and "optional" all mean that they can be included or not (or can be included or not).
[0086] Glossary and test methods:
[0087] Base glass: refers to glass that has not been nucleated, crystallized or strengthened.
[0088] Glass-ceramics: also known as glass ceramics, is a type of solid composite material that contains both a glass phase and a crystal phase (also called a microcrystalline phase or a crystalline phase) and is prepared by targeted and controlled crystallization of the base glass.
[0089] Transparent microcrystalline glass: refers to microcrystalline glass that is transparent in the visible light range.
[0090] Chemically strengthened glass-ceramics: It is a solid composite material obtained after chemical strengthening treatment of glass-ceramics. During high-temperature chemical strengthening treatment, the alkali metal ions with large ionic radius (such as potassium ions and sodium ions) in the molten salt bath will replace the alkali metal ions with small ionic radius (such as sodium ions and lithium ions) in the glass-ceramics, thereby generating a volume difference of exchange ions and generating compressive stress on the surface of the glass-ceramics.
[0091] Main crystalline phase: refers to a crystalline phase having a higher weight content than other crystalline phases present in the transparent glass-ceramics.
[0092] Main surface: refers to the surface with the largest surface area in the glass brick or glass sheet, such as the upper and lower surfaces of the cover glass.
[0093] Transmittance: The ratio of the radiant energy that is projected and passes through an object to the total radiant energy that is projected onto the object during the process of the incident light flux leaving from the illuminated surface or the incident surface of the medium to the other side.
[0094] b value: belongs to the Lab color model, a color model developed by the International Illumination Commission. Positive and negative b values represent yellow and blue.
[0095] Haze: Haze is the percentage of transmitted light intensity that deviates from the incident light by more than 2.5° to the total transmitted light intensity.
[0096] Nucleation: Through heat treatment, the nucleating material in the glass grows small crystal nuclei.
[0097] Crystallization: Through heat treatment, glass is made to grow certain crystals based on the crystal nucleus.
[0098] Flowery pieces: refers to the situation where the main surface of the glass piece shows partial coloration and / or the overall coloration of the glass piece is uneven when strong light enters the glass piece from the side. Fig.14 As shown in the figure, products with flower chips are defined as defective products during the production process because they cannot meet the display requirements of the display cover glass.
[0099] Precursor: A form of existence before obtaining the target object.
[0100] Glass transition temperature: Tg, unit ℃, also known as the brittle temperature of glass, it is the highest temperature at which glass becomes brittle, and the corresponding viscosity is 10 12 Pa·s, also known as the upper limit of annealing temperature, at this temperature, the internal stress of glass products caused by uneven cooling can be eliminated. Tg is obtained through the heating DSC curve of the substrate glass. It is manifested in the step of the baseline changing in the direction of heat absorption on the DSC curve. The two baseline extension lines before and after the step are tangent to the inflection point of the curve. The average value of the corresponding temperature of the two intersection points is the glass transition temperature.
[0101] CS_50: refers to the compressive stress value at a depth of 50μm measured from the main surface of the chemically strengthened microcrystalline glass.
[0102] DOL_0: Depth of compressive stress layer, also known as depth of compressive stress layer, refers to the distance from any surface of the glass to the position close to the surface where the compressive stress is zero in the direction of the glass thickness.
[0103] |CT_AV|: The absolute value of the average tensile stress in the tensile stress layer, specifically refers to the absolute value of the average value of all tensile stresses in the tensile stress layer.
[0104] Test conditions for CS_50, |CT_AV|, and DOL_0: Use SLP-2000 from Orihara, Japan, with a light source wavelength of 518nm, SOC=25.5 (nm / cm) / MPa, refractive index=1.54, and exposure time: 300usec.
[0105] When testing the surface CS_50, |CT_AV|, and DOL_0, it is necessary to first drop a conductive liquid on the stress meter, then wipe the chemically strengthened microcrystalline glass sample to be tested clean, place it on the test path, and test its stress value. The stress meter is SLP-2000 and the conductive liquid used is a conductive liquid with a refractive index of 1.51.
[0106] Optical property test of glass-ceramics with a thickness of more than 2 mm: The YJD-3600C haze meter is used to test the b-values of different parts of the main surface of the glass-ceramics, and the b-value range data and b-value average data of nine locations are obtained. In this application, the test aperture of the YJD-3600C haze meter used is 16.5 mm, and the instrument complies with the dual standards of ASTM D1003 / D1044 and ISO13468 / ISO14782. To ensure accuracy, this test method is suitable for testing glass-ceramics with a thickness of more than 2 mm. In this application, the transmission mode of the YJD-3600C haze meter is selected to test the optical properties of glass-ceramics.
[0107] Optical performance test of microcrystalline glass with a thickness of less than 2 mm: This application uses the spectrophotometer CM-3600A of Konica Minolta of Japan to test the haze, L value, a value, and b value of microcrystalline glass. The test aperture of the spectrophotometer CM-3600A used is 25.6 mm. This application uses Shimadzu's UV-2000 ultraviolet visible spectrophotometer to test the transmittance and its curve. To ensure accuracy, this test method is suitable for testing glass sheets with a thickness of less than 2 mm. In this application, the transmission mode of the spectrophotometer CM-3600A is selected to test the optical properties of microcrystalline glass.
[0108] Synchronous thermal analysis test: Use Mettler Toledo TGA / DSC3+ synchronous thermal analyzer to test according to the required process. The obtained curve is called DSC curve, including heating DSC curve and cooling DSC curve.
[0109] Test conditions for the temperature-increasing DSC curve: After grinding the substrate glass, sieve through 200 mesh to obtain the sample to be tested, weigh about 20 mg of the sample, and heat it from room temperature to 900°C at a heating rate of 10°C / min under a nitrogen atmosphere to obtain the temperature-increasing DSC curve of the sample. The differential thermal analysis instrument used in this application to test the temperature-increasing DSC curve is a Mettler-Toledo TGA / DSC3+ synchronous thermal analyzer, the standard used in the test is α-Al2O3 powder, the container for placing the sample is a platinum crucible, the ambient temperature of the instrument is 24°C, and the air humidity is 40%.
[0110] Test conditions for cooling DSC curve: After grinding the substrate glass, sieve it through 200 mesh to obtain the sample to be tested, weigh about 20 mg of the sample, and heat it from room temperature to 1400°C at a heating rate of 10°C / min under a nitrogen atmosphere. After keeping warm for 10 minutes, cool it to 450°C at 10°C / min to obtain the cooling DSC curve of the sample. The cooling DSC curve is processed by origin 2022b software, and the sum of the integral areas of the endothermic peak and the exothermic peak on the curve can be obtained by Gaussian fitting. The differential thermal analysis instrument used in this application to test the cooling DSC curve is a Mettler-Toledo TGA / DSC3+ synchronous thermal analyzer. The standard used in the test is α-Al2O3 powder, the container for placing the sample is a platinum crucible, the ambient temperature of the instrument is 24°C, and the air humidity is 40%.
[0111] Glass thickness: measured by laser thickness gauge.
[0112] Glass sheet size specification measurement: Use a two-dimensional measuring machine (instrument model: MiyuMY-YXCL-4030) for testing. Place the glass sheet to be tested on the measuring table of the two-dimensional measuring machine, set the program, and the instrument will automatically grab and measure the length and width of the glass sheet.
[0113] XRD test: The microcrystalline glass was crushed and ground into samples with a particle size of less than 75 μm, and the ground samples were tested using an X-ray diffractometer to obtain the XRD diffraction peak curve and XRD diffraction data. The X-ray diffractometer was Shimadzu XRD-6100, the incident angle range used in the test was 2θ=10-80°, the scanning speed was 3° / min, the operating voltage was 40 kV, and the operating current was 30 mA.
[0114] Determination of crystal phase: The XRD test results (RAW format) are imported into the X-ray diffraction data Rietveld refinement software JADE Standard 8.6 for fitting and analysis to determine the crystal phase in the microcrystalline glass sample.
[0115] The crystal content in this application refers to the percentage of crystals or crystalline phases in the mass of microcrystalline glass, which is a weight percentage.
[0116] Determination of crystal content: Import the XRD test results (RAW format) into the X-ray diffraction data Rietveld refinement software JADE Standard 8.6 for fitting and calculation to obtain the crystal content in the microcrystalline glass sample. Specifically, the ratio of the fitted crystal phase peak area to the fitted total peak area is the crystal content.
[0117] Average crystal size test: The result data obtained by XRD test can be used to calculate the average crystal size of the sample according to the Scherrer formula D = Kλ / (βcosθ). Wherein, λ is the X-ray wavelength, λ = 0.154056nm, β is the half-height width of the diffraction peak, K = 0.89, and θ is the Bragg diffraction angle. Specifically, the RAW file (diffraction spectrum) output by the XRD instrument is curve-fitted in the JADE Standard 8.6 software, and Jade outputs the fitting report. According to the angle 2θ value and Peak FWHM value (half-height width of the diffraction peak) corresponding to each diffraction peak in the fitting report, and the Peak FWHM value is converted into radians: β = (FWHM / 180×3.14), the grain size of each diffraction peak is calculated by the Scherrer formula D = Kλ / (βcosθ) and then averaged to obtain the average crystal size.
[0118] Surface Na2O concentration test: Surface Na2O concentration is equal to surface Na2O mass / total surface oxide mass, where the total surface oxide mass includes oxides such as SiO2, Al2O3, P2O5, ZrO2, Na2O, K2O, CaO that can be accurately tested by XRF, but does not include the content of oxides such as Li2O and B2O3 that cannot be accurately tested by XRF. The surface Na2O concentration of the chemically strengthened microcrystalline glass of this application is measured by X-ray fluorescence spectrometer (XRF), and the test equipment used is ThermoScientificARL TM PERFORM'X. The target material is Rh (rhodium), the light tube voltage is 40KW, the current is 60mA, the collimator is 0.15, the crystal is LiF200, the detector is FPC, the test range is 29mm circle, and the analysis software is UniQuant standardless analysis. Standardless testing is used during XRF testing, and the concentration of elements or their oxides with atomic numbers 6 and below in the glass is not tested. That is, in this application, when the surface Na2O concentration is tested by XRF, the total mass of the surface oxide does not include the mass of elements or their oxides with atomic numbers 6 and below in the glass.
[0119] Fixed height drop test:
[0120] (1) Stick 120-grit sandpaper on the bottom surface of the 187g model machine and place the model machine on the Wonder Inno drop test machine;
[0121] (2) Place a glass-ceramic sample to be tested with a length, width and thickness of 50 mm × 50 mm × 0.6 mm on a smooth marble plate directly below the model machine, with the glass-ceramic sample facing the sandpaper;
[0122] (3) Drop the model machine from a fixed height of 1.0 m to impact the glass-ceramic sample directly below the model machine. If the glass-ceramic sample is not broken, replace the sandpaper on the lower surface of the model machine and repeat the above drop impact process until the glass-ceramic breaks, and record the number of drops when it breaks.
[0123] At least 10 identical glass-ceramic samples are taken from each batch for a fixed-point height drop test, and the average value of the test results of the 10 glass-ceramic samples is calculated to characterize the drop resistance of the glass-ceramic.
[0124] As described above, in some embodiments of the present application, a transparent microcrystalline glass and a substrate glass for preparing the transparent microcrystalline glass are provided. The substrate glass can be prepared into the transparent microcrystalline glass by heat treatment. Therefore, it can be understood that, in terms of oxides, the composition of the substrate glass is the same as that of the transparent microcrystalline glass.
[0125] In some embodiments of the present application, the transparent glass-ceramics contains a main crystalline phase of petalite (LiAlSi4O 10 ) crystal phase and the main crystal phase lithium disilicate (Li2Si2O5) crystal phase. The "main crystal phase" here means that the crystal phase content in the transparent microcrystalline glass of the present application accounts for the majority, that is, the petalite crystal phase and the lithium disilicate crystal phase have a higher weight percentage than other crystal phases present in the transparent microcrystalline glass.
[0126] In some embodiments of the present application, the composition of the transparent microcrystalline glass or substrate glass includes, in terms of molar percentage of oxides: SiO2: 60.90mol%-72.65mol%, Al2O3: 1.50mol%-5.00mol%, P2O5: 0.85mol%-1.50mol%, ZrO2: 2.00mol%-4.00mol%, Na2O: 0.00mol%-1.00mol%, K2O: 0.00mol%-0.50mol%, Li2O: 20.00mol%-30.00mol%, CaO:
[0127] 0.00mol%-1.60mol%, B2O3: 0.00mol%-1.00mol%;
[0128] The composition of the transparent glass-ceramics or substrate glass satisfies the following conditions, expressed in terms of the molar percentage of each oxide in the composition of the transparent glass-ceramics or substrate glass:
[0129] 18.200≤Li2O / P2O5≤25.500;
[0130] 14.000≤2×Li2O / (0.5×ZrO2+CaO)≤23.000. By satisfying the oxide content under specific conditions and the specific oxide content relationship, not only can the generation of the main crystalline phases of petalite and lithium disilicate be guaranteed, but also the problem of overall bluish, foggy and even cracking of the microcrystalline glass bricks can be avoided when the microcrystalline glass bricks are prepared from large-sized substrate glass bricks while ensuring the good melting condition of the substrate glass bricks. This is conducive to the transparent microcrystalline glass to obtain excellent optical properties and strength, and thus the overall display effect of the transparent microcrystalline glass can meet the application requirements of the display cover. At the same time, the transparent microcrystalline glass of the present application can obtain high-strength chemically strengthened microcrystalline glass after chemical strengthening treatment.
[0131] In the glass system of the present application, SiO2 is an oxide that forms the glass network skeleton, which is used to stabilize the network structure of the substrate glass and microcrystalline glass, and is an important component of the crystal phases such as lithium silicate, petalite, β-spodumene and quartz. When the SiO2 content is too little, the glass tends to have a higher thermal expansion coefficient and reduced thermal shock resistance; when the SiO2 content is too much, the glass's solubility will deteriorate, or the viscosity of the molten glass will increase, making the glass difficult to clarify, making the glass more difficult to form, reducing productivity, and also causing the crystallization heat treatment time of the substrate glass to become longer. In the present application, the transparent microcrystalline glass or substrate glass contains 60.90mol%-72.65mol% SiO2.
[0132] In some embodiments, the transparent microcrystalline glass or substrate glass may contain 60.90mol%-72.65mol%, 60.90mol%-72.00mol%, 60.90mol%-71.00mol%, 60.90mol%-70.00mol%, 60.90mol%-69.00mol%, 60.90mol%-68.00mol%, 62.00mol%-72.00mol%, 63.00mol%-72.00mol%, 64.00mol%-72.00mol%, 65.00mol%-72.00mol%, 66.00mol%-72.00mol%, 67.00mol%-72.00mol% or 67.50mol%-71.00mol% SiO2. In some embodiments, the transparent glass-ceramics or substrate glass may contain 60.90 mol%, 62.00 mol%, 63.00 mol%, 64.00 mol%, 65.00 mol%, 66.00 mol%, 67.00 mol%, 67.50 mol%, 68.00 mol%, 69.00 mol%, 70.00 mol%, 71.00 mol%, 72.00 mol% or 72.65 mol% of SiO2, or SiO2 within a numerical range consisting of any two of the above specific values as endpoints. It should be understood that, in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the transparent glass-ceramics or substrate glass with the required performance of the present application can be obtained.
[0133] In the glass system of the present application, Al2O3 can be used to construct the glass skeleton and is an indispensable component for forming petalite. Al2O3 is coordinated around the crystal nucleus to form a "center-shell" structure. This structure makes it difficult for the crystal nucleus components to be supplied from the outer part of the shell, and the crystal nucleus is not easy to grow, and it is easy to form multiple tiny grains. When the Al2O3 content is too little, the glass has a tendency to increase its thermal expansion coefficient, its chemical durability is reduced, and the crystal nucleus is easy to become larger, and the microcrystalline glass is prone to white turbidity; when the Al2O3 content is too much, the glass's solubility deteriorates, production becomes difficult, and mullite crystals are easily precipitated to make the glass devitrified. In the glass system of the present application, the transparent microcrystalline glass or the substrate glass contains 1.50mol%-5.00mol% of Al2O3. Al2O3 that meets this content range is conducive to stabilizing the glass network structure, improving the mechanical properties and chemical durability of the transparent microcrystalline glass, and inhibiting the phase separation of the glass, reducing the thermal expansion coefficient and increasing the strain point.
[0134] In some embodiments, the transparent glass-ceramics or substrate glass may contain 1.50mol%-5.00mol%, 3.50mol%-5.00mol%, 3.50mol%-4.00mol%, 3.50mol%-4.50mol%, 4.00mol%-5.00mol% or 4.50mol%-5.00mol% Al2O3. In some embodiments, the transparent glass-ceramics or substrate glass may contain 1.50mol%, 2.00mol%, 2.50mol%, 3.00mol%, 3.50mol%, 4.00mol%, 4.50mol% or 5.00mol% Al2O3, or Al2O3 within the numerical range formed by any two of the above specific values as endpoints. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the transparent glass-ceramics or substrate glass with the required performance of the present application can be obtained.
[0135] In the glass system of the present application, Li2O is the main component of the petalite crystal phase and the lithium silicate crystal phase, and is also a necessary component for chemical strengthening. When the Li2O content is too little, it is easy to cause the glass to have a lower meltability or higher viscosity, making it difficult to clarify the glass liquid, making it difficult to form the substrate glass, and causing the glass to easily precipitate crystalline phases, such as mullite, which causes the glass to become devitrified; and when the Li2O content is too much, the crystallization ability of the glass becomes too strong, the glass has a tendency to become devitrified, and the microcrystalline glass becomes easily broken. In the glass system of the present application, the transparent microcrystalline glass or the substrate glass contains 20.00 mol%-30.00 mol% of Li2O. Li2O that meets this content range is conducive to ensuring that the transparency, melting and crystallization ability of the microcrystalline glass meet the requirements.
[0136] In some embodiments, the transparent microcrystalline glass or the substrate glass may contain 20.00mol%-30.00mol%, 20.00mol%-25.00mol%, 20.00mol%-24.00mol%, 20.00mol%-23.00mol%, 20.00mol%-22.00mol%, 20.00mol%-21.00mol% or 21.00mol%-23.00mol% Li2O. In some embodiments, the transparent glass-ceramics or substrate glass may contain 20.00 mol%, 21.00 mol%, 22.00 mol%, 23.00 mol%, 24.00 mol%, 25.00 mol%, 26.00 mol%, 27.00 mol%, 28.00 mol% or 30.00 mol% of Li2O, or Li2O within a numerical range consisting of any two of the above specific values as endpoints. It should be understood that, in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the transparent glass-ceramics or substrate glass with the required performance of the present application can be obtained.
[0137] In the glass system of the present application, P2O5 is a glass-forming oxide, which exists in the network structure as a phosphorus-oxygen tetrahedron [PO4]. P2O5 appears preferentially during the heat treatment process, first causing the glass to phase-segregate and form an amorphous precursor phase Li3PO4, and then using Li3PO4 as a non-uniform nucleation point, crystalline phases such as lithium silicate grow by adhering to the amorphous Li3PO4. With the increase of the P2O5 content, the non-uniform nucleation points increase, and the grains with Li3PO4 as the nucleation point are effectively refined, which is beneficial to improving the overall transmittance of microcrystalline glass, the uniformity of the glass and reducing the b value. However, when the P2O5 content is too much, the crystallization upper limit temperature increases, and it is easy to generate more Li3PO4 crystals, so that the Li2O content of lithium silicate and petalite is insufficient, which leads to the substrate glass being easy to precipitate quartz crystals, causing the transmittance of microcrystalline glass to decrease, the optical uniformity of the microcrystalline glass as a whole to decrease, and even worse, causing the substrate glass to directly crystallize during melt molding. When the content of P2O5 is too low, coarse ZrO2 crystals will be easily precipitated to cause the glass to lose transparency. In the glass system of the present application, the transparent microcrystalline glass or substrate glass contains 0.85mol%-1.50mol% of P2O5. This content range of P2O5 is conducive to ensuring high transmittance and good optical uniformity of the microcrystalline glass, and is conducive to significantly reducing the b value, so that the gain effect is optimal.
[0138] In some embodiments, the transparent glass-ceramics or substrate glass may contain 0.85mol%-1.50mol%, 0.85mol%-1.40mol%, 0.85mol%-1.30mol%, 0.85mol%-1.20mol%, 0.85mol%-1.10mol%, 0.85mol%-1.00mol% or 1.00mol%-1.30mol% of P2O5. In some embodiments, the transparent glass-ceramics or substrate glass may contain 0.85mol%, 0.95mol%, 1.00mol%, 1.10mol%, 1.20mol%, 1.30mol%, 1.40mol% or 1.50mol% of P2O5, or P2O5 within a numerical range consisting of any two of the above specific numerical values as endpoints. It should be understood that, in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as a transparent microcrystalline glass or substrate glass with the required performance of the present application can be obtained.
[0139] In the glass system of the present application, since P2O5 preferentially generates amorphous Li3PO4 during heat treatment, the increase of P2O5 will inevitably compete for more Li2O, thereby reducing the production of lithium silicate and petalite, so a certain degree of Li2O needs to be supplemented. In this regard, in the system of the present application, the composition of the transparent microcrystalline glass or substrate glass, expressed in terms of the molar percentage of each oxide in the composition of the transparent microcrystalline glass or substrate glass, satisfies: 18.200≤Li2O / P2O5≤25.500, where the chemical formula represents the molar percentage of the oxide, which is conducive to ensuring the production of the main crystalline phase and improving the strength performance of the glass. In some embodiments, the value of Li2O / P2O5 can be, for example, 18.200, 18.300, 18.400, 18.500, 18.600, 18.700, 18.800, 18.900, 19.000, 19.100, 19.200, 19.300, 19.400, 19.500, 19.600, 19.700, 19.800, 19.900、20.000、20.100、20.200、20.300、20.400、20.500、20.600、20.700、20.800、20.900、21.000、21.100、21.200、21.300、21.400、21.500、21.600、21.700、21.800、21.9 00, 22.000, 22.100, 22.200, 22.300, 22.400, 22.500, 22.600, 22.700, 22.800, 22.900, 23.000, 23.100, 23.200, 23.300, 23.400, 23.500, 23.600, 23.700, 23.800, 23.900, 2 400, 24.500, 24.600, 24.700, 24.800, 24.900, 25.000, 25.100, 25.200, 25.300, 25.400 or 25.500, or a value within a numerical range consisting of any two of the above specific values as endpoints.
[0140] In the glass system of the present application, an appropriate amount of ZrO2 exists in the residual glass phase after heat treatment, which is beneficial to improving the mechanical properties of the microcrystalline glass. However, excessive ZrO2 will increase the difficulty of melting the substrate glass, and easily lead to the formation of white zirconium precipitates in the substrate glass, which is not conducive to the production of transparent microcrystalline glass. In the glass system of the present application, the transparent microcrystalline glass or the substrate glass contains 2.00mol%-4.00mol% of ZrO2. ZrO2 that meets this content range is conducive to the production of transparent microcrystalline glass and improves the mechanical properties of transparent microcrystalline glass.
[0141] In some embodiments, the transparent microcrystalline glass or substrate glass may contain 2.00mol%-4.00mol%, 2.50mol%-3.50mol%, 2.50mol%-3.30mol%, 2.50mol%-3.10mol%, 2.50mol%-3.00mol%, 2.50mol%-2.80mol%, 2.80mol%-3.50mol%, 2.80mol%-3.40mol%, 2.80mol%-3.30mol% or 2.80mol%-3.10mol% ZrO2. In some embodiments, the transparent glass-ceramics or substrate glass may contain 2.00 mol%, 2.50 mol%, 2.70 mol%, 2.90 mol%, 3.00 mol%, 3.10 mol%, 3.30 mol%, 3.50 mol% or 4.00 mol% ZrO2, or ZrO2 within a numerical range consisting of any two of the above specific values as endpoints. It should be understood that, in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the transparent glass-ceramics or substrate glass having the performance required by the present application can be obtained.
[0142] In the glass system of the present application, an appropriate amount of B2O3 helps to reduce the melting temperature of the base glass. B2O3 has boron-oxygen triangles [BO3] and boron-oxygen tetrahedrons [BO4] as structural units. As the content of B2O3 increases, the relative content of boron-oxygen triangles and boron-oxygen tetrahedrons changes, resulting in a reversal of structure and properties. When too much B2O3 is added, on the one hand, the three-dimensional framework structure of the boron-oxygen tetrahedron [BO4] is transformed into a two-dimensional layered structure of the boron-oxygen triangle [BO3], and the three-coordinated boron-oxygen triangle [BO3] is not as strong as the boron-oxygen tetrahedron [BO4], which will have the effect of opening the network structure. At the same time, the increase in the B2O3 content in the residual glass phase will reduce the viscosity of the residual glass phase and promote the growth of crystals such as lithium silicate; on the other hand, the base glass is more likely to precipitate SiO2 crystal phases (such as quartz), which will affect the glass transmittance and deteriorate the overall uniformity of the glass brick. In the glass system of the present application, the transparent microcrystalline glass or substrate glass contains 0.00 mol%-1.00 mol% B2O3. B2O3 that meets this content range helps to lower the melting temperature of the substrate glass and improve the transmittance, overall uniformity and other properties of the microcrystalline glass.
[0143] In some embodiments, the transparent microcrystalline glass or substrate glass may contain 0.00mol%-1.00mol%, 0.00mol%-0.90mol%, 0.00mol%-0.80mol%, 0.00mol%-0.70mol%, 0.00mol%-0.60mol%, 0.00mol%-0.50mol%, 0.00mol%-0.40mol%, 0.20mol%-1.00mol%, 0.30mol%-0.80mol% or 0.30mol%-0.50mol% B2O3. In some embodiments, the transparent glass-ceramics or substrate glass may contain 0.00 mol%, 0.10 mol%, 0.20 mol%, 0.30 mol%, 0.40 mol%, 0.50 mol%, 0.70 mol%, 0.90 mol% or 1.00 mol% B2O3, or B2O3 within a numerical range consisting of any two of the above specific values as endpoints. It should be understood that, in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the transparent glass-ceramics or substrate glass having the performance required by the present application can be obtained.
[0144] In the glass system of the present application, Na2O and K2O are oxides outside the glass network, which can provide free oxygen and increase the oxygen-silicon ratio in the glass structure. Therefore, too much Na2O and K2O will affect the network structure of the glass, and affect the optical properties, thermal stability, chemical stability, mechanical strength and weather resistance of the glass. However, in the glass system of the present application, an appropriate amount of Na2O and K2O can bring certain beneficial effects. For example, an appropriate amount of Na2O can play a role in adjusting the grain size, promoting the crystallization of the lithium silicate structure, and reducing the crystallization tendency of the substrate glass, thereby appropriately increasing the transmittance of the microcrystalline glass, and appropriately improving the thermal stability, chemical stability, mechanical strength, weather resistance, etc. of the microcrystalline glass. Therefore, in the glass system of the present application, it is preferred that the transparent microcrystalline glass or the substrate glass contain 0.00mol%-1.00mol% Na2O and 0.00mol%-0.50mol% K2O.
[0145] In some embodiments, the transparent microcrystalline glass or substrate glass may contain 0.00mol%-1.00mol%, 0.00mol%-0.90mol%, 0.00mol%-0.80mol%, 0.00mol%-0.70mol%, 0.00mol%-0.60mol%, 0.00mol%-0.50mol%, 0.00mol%-0.40mol%, 0.20mol%-1.00mol%, 0.30mol%-0.80mol% or 0.30mol%-0.50mol% Na2O. In some embodiments, the transparent glass-ceramics or substrate glass may contain 0.00 mol%, 0.10 mol%, 0.20 mol%, 0.30 mol%, 0.40 mol%, 0.50 mol%, 0.70 mol%, 0.90 mol% or 1.00 mol% of Na2O, or Na2O within a numerical range consisting of any two of the above specific values as endpoints. It should be understood that, in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the transparent glass-ceramics or substrate glass having the performance required by the present application can be obtained.
[0146] In some embodiments, the transparent glass-ceramics or substrate glass may contain 0.00mol%-0.50mol%, 0.00mol%-0.40mol%, 0.00mol%-0.30mol%, 0.00mol%-0.20mol%, 0.00mol%-0.10mol%, 0.10mol%-0.50mol% or 0.20mol%-0.40mol% K2O. In some embodiments, the transparent glass-ceramics or substrate glass may contain 0.00mol%, 0.10mol%, 0.20mol%, 0.30mol%, 0.40mol% or 0.50mol% K2O, or K2O within a numerical range consisting of any two of the above specific values as endpoints. It should be understood that, in a specific embodiment, any of the above ranges may be combined with any other ranges, as long as the transparent glass-ceramics or substrate glass having the required performance of the present application can be obtained.
[0147] In the glass system of the present application, an appropriate amount of CaO is beneficial to increase the chemical stability and mechanical strength of the glass, reduce the viscosity of the glass, enhance the solubility and formability of the glass, and is also beneficial to adjust the thermal expansion coefficient and refractive index of the microcrystalline glass. However, when the CaO content is too much, the glass is prone to devitrification after crystallization treatment, and too much CaO residue in the glass phase produces a refractive index difference with the main crystal phase, which will cause the transmittance of the microcrystalline glass to decrease and the haze to increase. In the glass system of the present application, the transparent microcrystalline glass or the substrate glass contains 0.00mol%-1.60mol% CaO.
[0148] In some embodiments, the transparent microcrystalline glass or substrate glass may contain 0.00mol%-1.60mol%, 0.50mol%-1.60mol%, 0.50mol%-1.50mol%, 0.50mol%-1.30mol%, 0.50mol%-1.20mol%, 0.50mol%-1.00mol%, 0.50mol%-0.85mol%, 0.85mol%-1.40mol%, 0.85mol%-1.30mol%, 0.85mol%-1.20mol%, 0.85mol%-1.10mol%, 0.85mol%-1.00mol% or 1.00mol%-1.30mol% CaO. In some embodiments, the transparent glass-ceramics or substrate glass may contain 0.00 mol%, 0.50 mol%, 0.70 mol%, 0.85 mol%, 0.95 mol%, 1.00 mol%, 1.10 mol%, 1.20 mol%, 1.30 mol%, 1.40 mol%, 1.50 mol% or 1.60 mol% of CaO, or CaO within a numerical range consisting of any two of the above specific values as endpoints. It should be understood that, in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the transparent glass-ceramics or substrate glass with the required performance of the present application can be obtained.
[0149] In the glass system of the present application, the composition of the transparent microcrystalline glass or the substrate glass, expressed in terms of the content expressed in molar percentage of each oxide in the composition of the transparent microcrystalline glass or the substrate glass, satisfies: 14.000≤2×Li2O / (0.5×ZrO2+CaO)≤23.000, where the chemical formula represents the molar percentage of the oxide, which is conducive to the mass production of large-sized transparent microcrystalline glass with satisfactory optical properties. In some embodiments, the value of 2×Li2O / (0.5×ZrO2+CaO) can be, for example, 14.000, 15.000, 16.000, 17.000, 18.000, 19.000, 20.000, 21.000, 22.000 or 23.000, or can be a value within a numerical range consisting of any two of the above specific values as endpoints.
[0150] In some embodiments, the composition of the transparent glass-ceramics or substrate glass, expressed as the molar percentage of each oxide in the composition of the transparent glass-ceramics or substrate glass, satisfies: 4.100≤(Li2O+Na2O+K2O+B2O3) / (P2O5+ZrO2+CaO)≤6.000, where the chemical formula represents the molar percentage of the oxide, thereby facilitating the formation of a transparent glass-ceramics that meets a specific structure and has excellent performance (especially optical and strength performance). In some embodiments,
[0151] The value of (Li2O+Na2O+K2O+B2O3) / (P2O5+ZrO2+CaO) can be, for example, 4.100, 4.200, 4.300, 4.400, 4.500, 4.600, 4.700, 4.800, 4.900, 5.000, 5.100, 5.200, 5.300, 5.400, 5.500, 5.600, 5.700, 5.800, 5.900 or 6.000 and any value between these adjacent point values, or it can be a value within the numerical range formed by any two of the above specific values as endpoints.
[0152] In some embodiments, the composition of the transparent glass-ceramics or the substrate glass, expressed in terms of the molar percentage of each oxide in the composition, satisfies the following conditions: 0.100≤P2O5×(CaO+ZrO2+Li2O+Al2O3) / (Na2O+K2O+B2O3)≤0.900, preferably 0.190≤P2O5×(CaO+ZrO2+Li2O+Al2O3) / (Na2O+K2O+B2O3)≤0.900, wherein the chemical formula represents the molar percentage of the oxide, thereby facilitating the formation of a transparent glass-ceramics satisfying a specific structure and having excellent properties (especially optical and strength properties). In some embodiments, the value of P2O5×(CaO+ZrO2+Li2O+Al2O3) / (Na2O+K2O+B2O3) can be, for example, 0.100, 0.200, 0.300, 0.400, 0.500, 0.600, 0.700, 0.800 or 0.900, or can be a value within a numerical range consisting of any two of the above specific values as endpoints.
[0153] In some preferred embodiments, the composition of the transparent glass-ceramics or substrate glass includes, in terms of molar percentage of oxides: SiO2: 67.50 mol%-71.00 mol%, Al2O3:
[0154] 3.50mol%-5.00mol%, P2O5: 0.85mol%-1.50mol%, ZrO2:
[0155] 2.50mol%-3.50mol%, Na2O: 0.00mol%-1.00mol%, K2O: greater than 0.00mol% and not greater than 0.50mol%, Li2O: 20.00mol%-25.00mol%, CaO: greater than 0.50mol% and not greater than 1.60mol%, B2O3: 0.00mol%-1.00mol%. By adjusting the content relationship of the necessary oxides, it is beneficial to further improve the network structure of the microcrystalline glass, thereby ensuring the large-scale mass production effect of transparent microcrystalline glass and ensuring the excellent optical properties and strength properties of the mass-produced products.
[0156] In some embodiments, the transparent glass-ceramics does not contain quartz crystal phase. In the glass-ceramics whose main crystal phases are petalite crystal phase and lithium disilicate crystal phase, if quartz crystal phase is precipitated, the transmittance of the glass-ceramics will be reduced, affecting the optical properties of the glass-ceramics, and it is also easy to make the overall uniformity of the glass-ceramics bricks deteriorate, and then the b-values of different regions of the glass are different, and there are problems such as flower pieces. In some embodiments, the crystallinity of the transparent glass-ceramics is ≥70.00wt%, preferably, the crystallinity is ≥80.00wt%. Here, the "crystallinity of the transparent glass-ceramics" refers to the percentage of the content of all crystalline phases / crystals in the glass-ceramics to the mass of the glass-ceramics. A higher content of microcrystalline phase is beneficial to improving the mechanical strength performance of the glass-ceramics. In some embodiments, the crystallinity of the transparent glass-ceramics may be 70.00wt%, 75.00wt%, 80.00wt%, 85.00wt%, 90.00wt%, 93.00wt%, 95.00wt%, 98.00wt% or 100.00wt%, or a crystallinity within a numerical range consisting of any two of the above specific values as endpoints. It should be understood that, in a specific embodiment, any of the above ranges may be combined with any other ranges, as long as the transparent glass-ceramics having the desired performance of the present application can be obtained.
[0157] In some embodiments, in the transparent glass-ceramics, the average crystal size does not exceed 100nm. Meeting the smaller average crystal size is conducive to ensuring the excellent optical properties of the glass-ceramics. In some embodiments, the average crystal size can be 10nm, 20nm, 30nm, 40nm, 50nm, 60nm, 70nm, 80nm, 90nm or 100nm, or an average crystal size within a numerical range consisting of any two of the above specific values as endpoints. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the transparent glass-ceramics with the performance required by the present application can be obtained.
[0158] In some embodiments, in the transparent glass-ceramics, the petalite crystalline phase accounts for 35.00wt%-50.00wt% of the mass of the transparent glass-ceramics, and the lithium disilicate crystalline phase accounts for 35.00wt%-50.00wt% of the mass of the transparent glass-ceramics. In some embodiments, the percentage of the petalite crystalline phase in the mass of the transparent glass-ceramics can be 35.00wt%-50.00wt%, 35.00wt%-45.00wt%, 35.00wt%-40.00wt% or 40.00wt%-50.00wt%. In some embodiments, the transparent glass-ceramics may include 35.00wt%, 40.00wt%, 45.00wt% or 50.00wt% of the petalite crystalline phase, or the petalite crystalline phase is within the numerical range consisting of any two of the above specific values as endpoints. It should be understood that, in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the transparent microcrystalline glass with the required performance of the present application can be obtained. In some embodiments, the percentage of lithium disilicate crystalline phase in the mass of the transparent microcrystalline glass can be 35.00wt%-50.00wt%, 35.00wt%-45.00wt%, 35.00wt%-40.00wt% or 40.00wt%-50.00wt%. In some embodiments, the transparent microcrystalline glass may contain 35.00wt%, 40.00wt%, 45.00wt% or 50.00wt% of lithium disilicate crystalline phase, or a lithium disilicate crystalline phase within the numerical range consisting of any two of the above specific values as endpoints. It should be understood that, in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the transparent microcrystalline glass with the required performance of the present application can be obtained. By adjusting the petalite crystal phase and the lithium disilicate crystal phase to meet a suitable ratio, it is beneficial to form a specific microstructure, which in turn helps to ensure that the microcrystalline glass has high mechanical strength and fracture toughness.
[0159] In some embodiments, the transparent glass-ceramics contains one or more of a lithium silicate (Li2SiO3) crystal phase, a lithium phosphate (Li3PO4) crystal phase, and a spodumene crystal phase as a secondary crystalline phase. In some embodiments, in the transparent glass-ceramics, the secondary crystalline phase accounts for less than 30.00wt% of the mass of the transparent glass-ceramics, and preferably the secondary crystalline phase accounts for less than 10.00wt% of the mass of the transparent glass-ceramics. In the transparent glass-ceramics of the present application, the secondary crystalline phase content is low, which is more conducive to ensuring the high content of the main crystalline phase, and thus ensuring the excellent mechanical strength performance of the glass-ceramics. In some embodiments, the percentage of the secondary crystalline phase in the mass of the transparent glass-ceramics can be 0wt%, 5wt%, 10wt%, 15wt%, 20wt%, 25wt% or 30.00wt%, or a secondary crystalline phase within the numerical range formed by any two of the above specific values as endpoints. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the transparent glass-ceramics with the required performance of the present application can be obtained.
[0160] In some embodiments, in the transparent glass-ceramics, a lithium silicate crystal phase accounts for less than 5.00 wt% of the mass of the transparent glass-ceramics, and a total amount of a lithium phosphate crystal phase and a spodumene crystal phase accounts for less than 5.00 wt% of the mass of the transparent glass-ceramics.
[0161] In some embodiments, when the length, width and thickness specifications of the transparent microcrystalline glass are (200mm-500mm)×(100mm-500mm)×(10mm-40mm), the range of the b values at nine locations on the main surface of the transparent microcrystalline glass is ≤2.00, preferably ≤1.50, and more preferably ≤1.00. The "range of the nine b values" here refers to the difference between the maximum and minimum values of the b values at nine locations tested on the main surface of the glass. In some embodiments, the range of the b values at nine locations on the main surface of the transparent microcrystalline glass under this specification can be 0, 0.10, 0.50, 0.80, 1.00, 1.20, 1.50, 1.70, 1.80, 1.90 or 2.00, or a range within the numerical range formed by any two of the above specific values as endpoints. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the transparent microcrystalline glass with the required performance of the present application can be obtained. The smaller the range of the b values at nine points on the main surface of the microcrystalline glass that meets this specification, the better the overall uniformity and the better the optical effect of the microcrystalline glass of the present application when it is produced to this specification, which is beneficial to ensure that the cut microcrystalline glass sheets meet the requirements of excellent optical performance and display effects.
[0162] In some embodiments, when the length, width and thickness specifications of the transparent glass-ceramics are (45mm-450mm)×(45mm-350mm)×(0.4mm-2.0mm), the range of the b values at nine locations on the main surface of the transparent glass-ceramics is ≤0.30, preferably ≤0.10, preferably ≤0.06. In some embodiments, the range of the b values at nine locations on the main surface of the transparent glass-ceramics under this specification can be 0, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.10, 0.20 or 0.30, or a range within the numerical range formed by any two of the above specific values as endpoints. It should be understood that, in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as a transparent glass-ceramics with the performance required by the present application can be obtained. The smaller the range of the nine b values on the main surface of the microcrystalline glass sheet of this specification, the better the overall uniformity of the microcrystalline glass sheet of the present application and the better the overall display effect.
[0163] The nine positions are: (1) four test positions of the test circle I that is tangent to the long side and the adjacent short side on the main surface; (2) four test positions of the test circle II formed by the point on the line segment formed by the centers of the four test circles I that is closest to the middle of the long side or short side of the main surface; (3) one test circle III formed by the center point of the main surface as the center of the circle, such as Fig.13 As shown. In combination with the aforementioned b-value test method, it can be known that each tested point is a circle with a test aperture, and the center of the circle coincides with the above-mentioned test circle I, test circle II or test circle III.
[0164] In some embodiments, when the thickness of the transparent microcrystalline glass is 0.6 mm, the b value is ≤1.00, preferably the b value is ≤0.70, the haze is ≤0.25%, preferably the haze is ≤0.18%, and the transmittance of the transparent microcrystalline glass is ≥90.00% under the wavelength of 550 nm. In some preferred embodiments, when the thickness of the transparent microcrystalline glass is 0.6 mm, the b value is ≤0.60, the haze is ≤0.16%, and the transmittance of the transparent microcrystalline glass is ≥90.50% under the wavelength of 550 nm. The higher the transmittance, the smaller the b value and the haze, the better the optical properties of the microcrystalline glass.
[0165] In some embodiments, the transmittance of a 0.6 mm thick transparent glass-ceramic under 550 nm wavelength light can be 90.00%, 90.50%, 91.00%, 92.00%, 93.00%, 94.00%, 95.00%, 96.00%, 97.00%, 98.00%, 99.00% or 100.00%, or a transmittance within a numerical range consisting of any two of the above specific values as endpoints. It should be understood that in a specific embodiment, any of the above ranges can be combined with any other ranges as long as the transparent glass-ceramic with the required performance of the present application can be obtained. In some embodiments, the b value of a 0.6 mm thick transparent glass-ceramic can be 0, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9 or 1.0, or a value within a numerical range consisting of any two of the above specific values as endpoints. It should be understood that, in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the transparent microcrystalline glass with the required performance of the present application can be obtained. In some embodiments, the haze of a 0.6 mm thick transparent microcrystalline glass can be 0, 0.01%, 0.05%, 0.08%, 0.10%, 0.12%, 0.14%, 0.16%, 0.18%, 0.20% or 0.25%, or a haze within a numerical range consisting of any two of the above specific values as endpoints. It should be understood that, in a specific embodiment, any of the above ranges can be combined with any other ranges, as long as the transparent microcrystalline glass with the required performance of the present application can be obtained.
[0166] As described above, the extreme difference of the b values at nine locations on the main surface of the transparent microcrystalline glass of the present application is small, that is, the b values of different areas of the transparent microcrystalline glass of the present application are close; the transparent microcrystalline glass of the present application has high transmittance, low b value, and low haze, which all indicate that the optical properties of the transparent microcrystalline glass of the present application are excellent and uniform, and can meet the application requirements of display screen cover plates.
[0167] In some embodiments, through simultaneous thermal analysis testing, under a nitrogen protective atmosphere, the substrate glass is heated from room temperature to 900°C at a heating rate of 10°C / min to obtain a heating DSC curve, in which there are at least two exothermic peaks, wherein the first exothermic peak temperature T1 is 600°C-730°C, and the second exothermic peak temperature T2 is 740°C-800°C, and T1 and T2 satisfy the relationship: 100°C ≥ T2-T1 ≥ 40°C, preferably 80°C ≥ T2-T1 ≥ 50°C.
[0168] In some embodiments, through a simultaneous thermal analysis test, the substrate glass is heated from room temperature to 1400°C at a heating rate of 10°C / min and kept warm for 10 minutes under a nitrogen protective atmosphere, and then cooled from 1400°C to 450°C at a cooling rate of 10°C / min to obtain a cooling DSC curve. In the cooling DSC curve, within the range of 500°C-900°C, the sum of the integrated areas of the exothermic peaks and endothermic peaks contained therein is S≤10, preferably there is no endothermic peak and / or exothermic peak, and more preferably S=0.
[0169] Large-sized substrate glass bricks made of a specific substrate glass solution that meets specific DSC curve characteristics (including specific heating DSC curve characteristics and specific cooling DSC curve characteristics) are heat-treated under the production line process conditions for mass production of microcrystalline glass to produce transparent microcrystalline glass bricks whose optical properties and display effects meet the requirements for display screens. This can effectively solve the problems of glass brick cracking, large differences in b-values in different areas of glass bricks, localized unexpected colors, flower pieces, poor display, etc. that are prone to occur during mass production of microcrystalline glass bricks in the prior art. Therefore, before preparing large-sized microcrystalline glass bricks, glass samples can be made according to the glass formula. Through the obtained DSC curve characteristics, it can be verified whether the glass solution is suitable for the production of large-sized, especially thick qualified microcrystalline glass products. If it does not meet the requirements, it can be adjusted in time until it meets the specific DSC curve characteristics before large-sized preparation is carried out, which can greatly save time and cost and effectively avoid waste of resources.
[0170] In some embodiments, the substrate glass is heated from room temperature to T at a heating rate of 10°C / min. 1-30 temperature, and kept at this temperature for 240 minutes for treatment, wherein the content of quartz crystal phase in the product obtained after treatment is less than 15wt%; wherein T 1-30 =T1-30℃.
[0171] In some embodiments, the substrate glass is heated from room temperature to T at a heating rate of 10°C / min. 1-60 temperature, and kept at this temperature for 240 minutes for treatment, wherein the content of quartz crystal phase in the product obtained after treatment is less than 5wt%, preferably no quartz crystal phase; wherein T 1-60 =T1-60℃.
[0172] In T 1-30 and / or T 1-60 The substrate glass that meets the specific quartz crystal phase content requirements after heat treatment at a certain temperature can effectively avoid the precipitation of quartz crystal phases that affect the optical properties of the target microcrystalline glass bricks when the target microcrystalline glass is prepared by heat treatment, thereby ensuring the mass production of large-sized transparent microcrystalline glass bricks that meet the use requirements.
[0173] The preparation method or molding method of the substrate glass of the present application includes but is not limited to the float method, overflow method, rolling method, casting method or continuous melting method. In order to improve the yield, the present application preferably adopts the continuous melting method to prepare the substrate glass. The continuous melting method refers to a smelting method of continuous feeding and continuous furnace discharge. Specifically, the raw materials can be continuously fed into the melting furnace through an automatic feeding device, heated to 1500℃-1600℃, melted for 24-72 hours, and then pulled into shape, continuously drawn and cut into substrate glass products of any length.
[0174] The method for preparing the transparent microcrystalline glass of the present application comprises: heat treating the substrate glass as described above to obtain the transparent microcrystalline glass. The heat treatment conditions of the present application can be selected in a wide range, and those skilled in the art can select from the existing technology according to actual needs.
[0175] In some embodiments, the heat treatment includes a nucleation treatment and a crystallization treatment, wherein the temperature of the nucleation treatment is (Tg-20°C) to (Tg+40°C), for example, (Tg-20°C), (Tg-15°C), (Tg-10°C), (Tg-5°C), (Tg-2°C), Tg, (Tg+2°C), (Tg+5°C), (Tg+10°C), (Tg+15°C) or (Tg+40°C), or any value between these adjacent point values. Wherein, Tg is the glass transition temperature of the substrate glass.
[0176] In some embodiments, the time of nucleation treatment is 0 min-6000 min, for example, it can be 0 min, 30 min, 50 min, 70 min, 100 min, 130 min, 150 min, 180 min, 200 min, 250 min, 280 min, 300 min, 330 min, 360 min, 600 min, 800 min, 900 min, 1500 min, 2000 min or 6000 min, or any value between these adjacent point values.
[0177] In some embodiments, the temperature of the crystallization treatment is (T1-20°C) to (T1+20°C), for example, it can be (T1-20°C), (T1-15°C), (T1-10°C), (T1-5°C), (T1-2°C), T1, (T1+2°C), (T1+5°C), (T1+10°C), (T1+15°C) or (T1+20°C), or any value between these adjacent point values.
[0178] In some embodiments, the crystallization treatment time is 30 min-6000 min, for example, it can be 30 min, 50 min, 70 min, 100 min, 130 min, 150 min, 180 min, 200 min, 250 min, 280 min, 300 min, 330 min, 360 min, 400 min, 450 min, 500 min, 550 min, 600 min, 1000 min, 2000 min, 3000 min, 4000 min, 5000 min or 6000 min, or any value between these adjacent point values.
[0179] In some embodiments, the heating rate of the heat treatment process is 5-15°C / min, for example, 5°C / min, 8°C / min, 10°C / min, 12°C / min, 14°C / min or 15°C / min, or any value between these adjacent point values.
[0180] It should be understood that in the present application, the nucleation treatment is to heat up to a prescribed nucleation treatment temperature (also called nucleation temperature), and after reaching the nucleation treatment temperature, keep warm for a certain time, and the holding time here is the nucleation treatment time (also called nucleation time). The crystallization treatment is to heat up to a prescribed crystallization treatment temperature (also called crystallization temperature), and after reaching the crystallization treatment temperature, keep warm for a certain time, and the holding time here is the crystallization treatment time (also called crystallization time). The above-mentioned heat treatment conditions are conducive to the preparation of a transparent microcrystalline glass product with a specific microstructure and uniform structure, with petalite crystal phase and lithium disilicate crystal phase as the main crystal phase, and excellent optical and mechanical properties.
[0181] In some embodiments, the process of preparing transparent microcrystalline glass of the present application also includes a process of cold working the transparent microcrystalline glass (brick) obtained by heat treatment of the substrate glass to obtain a transparent microcrystalline glass of the required specifications and dimensions (e.g., a thickness of 0.2mm-2.0mm). The cold working treatment here includes shaping treatment, slicing treatment, CNC treatment, grinding treatment, polishing treatment, etc. commonly used in the art. Those skilled in the art can select one or more of the above methods to cold work the transparent microcrystalline glass according to actual needs.
[0182] The present application provides a chemically strengthened glass-ceramic, which is obtained by subjecting the transparent glass-ceramic as described above to chemical strengthening treatment. The composition at the center of the chemically strengthened glass-ceramic is substantially the same as that of the transparent glass-ceramic, and the chemically strengthened glass-ceramic includes a compressive stress layer region extending from the surface of the transparent glass-ceramic to a compression depth, and has tensile stress inside the chemically strengthened glass-ceramic.
[0183] After the chemical strengthening treatment, it should be understood that the composition at the surface of the glass-ceramic may be different from the composition of the newly formed glass-ceramic (i.e., the glass-ceramic has not been subjected to the ion exchange process before the chemical strengthening treatment). This is because during the chemical strengthening treatment, ion exchange occurs, and one type of alkali metal ion (e.g., Li + Or Na + ) are replaced by larger alkali metal ions (e.g., Na + or K + ) is replaced by, such as Na in glass-ceramics + K in molten salt bath + Exchange, K + Replaced by, and / or, Li in glass-ceramics + With Na in molten salt bath + Exchange, by Na + However, in the embodiment, the composition of the glass-ceramic at the center of the depth of the glass product or near the center of the depth will still have the composition of the newly formed glass-ceramic. That is, in the chemically strengthened glass-ceramic of the present application, the composition of the compressive stress layer formed by ion exchange on the surface may be different from the composition of the unstrengthened glass-ceramic, while the composition of the tensile stress layer with tensile stress (also called tensile stress) inside or the composition at the center of the glass-ceramic will still have the composition of the unstrengthened glass-ceramic.
[0184] In the present application, the chemical strengthening treatment conditions have a wide range of optional conditions, and those skilled in the art can select according to actual needs. In some embodiments, the chemical strengthening treatment salt bath is a mixed molten salt, and the composition of the mixed molten salt includes: 0<NaNO3<100wt%, 0<KNO3<100wt% and 0<LiNO3≤0.2wt%.
[0185] In various embodiments, based on the total amount of NaNO3 and KNO3 in the mixed molten salt, the mixed molten salt contains 0<NaNO3<100wt%. For example, the mixed molten salt may contain 20wt%-50wt%, 10wt%-50wt%, 10wt%-40wt%, 20wt%-40wt%, 20wt%-90wt% or 40wt%-90wt% NaNO3. In various embodiments, based on the total amount of NaNO3 and KNO3 in the mixed molten salt, the mixed molten salt contains 0<KNO3<100wt%. For example, the mixed molten salt may contain 20wt%-50wt%, 10wt%-50wt%, 10wt%-40wt%, 20wt%-40wt%, 20wt%-90wt% or 40wt%-90wt% KNO3. In various embodiments, based on the total amount of NaNO3 and KNO3 in the mixed molten salt, the mixed molten salt also contains 0<LiNO3≤0.2wt%. For example, the mixed molten salt may contain 0.01 wt%-0.20 wt%, 0.01 wt%-0.18 wt%, 0.01 wt%-0.15 wt%, 0.01 wt%-0.10 wt%, or 0.01 wt%-0.05 wt% of LiNO3.
[0186] In some embodiments, the temperature of the salt bath for chemical strengthening treatment is 430° C.-530° C., and the time of the chemical strengthening treatment is 0.5 h-15.0 h.
[0187] The use of the above-mentioned strengthening process for chemical strengthening is beneficial to improving the chemical strengthening efficiency while ensuring that the chemically strengthened glass-ceramics obtains the desired stress level.
[0188] In some embodiments, the temperature of the chemical strengthening salt bath may be 430°C, 440°C, 450°C, 460°C, 470°C, 480°C, 490°C, 500°C, 510°C, 520°C or 530°C, or may be a value within a numerical range consisting of any two of the above specific values as endpoints.
[0189] In some embodiments, the time of the chemical strengthening treatment can be 0.5h, 1.0h, 2.0h, 3.0h, 4.0h, 5.0h, 6.0h, 7.0h, 8.0h, 9.0h, 10.0h, 11.0h, 12.0h, 13.0h, 14.0h or 15.0h, or can be a value within a numerical range consisting of any two of the above specific values as endpoints.
[0190] In some embodiments, the surface Na2O concentration of the chemically strengthened glass-ceramics is 5.0wt%-20.0wt%. For example, the surface Na2O concentration of the chemically strengthened glass-ceramics can be 5.0wt%, 6.0wt%, 7.0wt%, 8.0wt%, 9.0wt%, 10.0wt%, 11.0wt%, 12.0wt%, 13.0wt%, 14.0wt%, 15.0wt%, 16.0wt%, 17.0wt%, 18.0wt%, 19.0wt% or 20.0wt%, or can be a value within a numerical range consisting of any two of the above specific values as endpoints. By satisfying the surface Na2O concentration within the above range, it can not only ensure that the chemically strengthened glass-ceramics has a better surface stress level, but also ensure that the chemically strengthened glass-ceramics has better weather resistance and chemical durability.
[0191] In some embodiments, the chemically strengthened glass-ceramics has a CS_50 of 110-200MPa, where CS_50 refers to the compressive stress value at a depth of 50μm from the main surface of the chemically strengthened glass-ceramics. For example, the chemically strengthened glass-ceramics has a CS_50 of 110-200MPa, 110-180MPa, 110-160MPa, 110-150MPa, 110-130MPa, 130-180MPa or 130-150MPa. The range of CS_50 of the chemically strengthened glass-ceramics is within the above range, indicating that the compressive stress of the chemically strengthened glass-ceramics at a depth of 50μm from the surface is high, indicating that the chemically strengthened glass-ceramics has a higher surface stress level, and the higher the surface compressive stress level, the more residual energy of the drop collision can be offset, thereby ensuring that it has excellent damage resistance. In some embodiments, the chemically strengthened glass-ceramics has a |CT_AV| of 84-140MPa, where |CT_AV| refers to the absolute value of the average tensile stress. For example, the chemically strengthened glass-ceramics has a |CT_AV| of 84-140MPa, 85-140MPa, 85-120MPa, 85-100MPa, 90-140MPa, 100-140MPa, or 120-140MPa. The |CT_AV| of the chemically strengthened glass-ceramics is within the above range, indicating that the chemically strengthened glass-ceramics has a higher tensile stress level, reflecting that it has a higher surface stress level, and the higher surface compressive stress level can offset the more residual energy of the drop collision, thereby ensuring that it has excellent damage resistance.
[0192] In some embodiments, the compressive stress layer depth DOL_0 of the chemically strengthened glass-ceramics is 0.18t-0.25t, where t is the thickness of the chemically strengthened glass-ceramics. For example, the compressive stress layer depth DOL_0 of the chemically strengthened glass-ceramics may be 0.18t-0.25t, 0.18t-0.22t, 0.18t-0.20t, 0.20t-0.25t or 0.22t-0.25t. Exemplarily, when the thickness of the chemically strengthened glass-ceramics is 0.6mm, the DOL_0 of the chemically strengthened glass-ceramics may be 0.108mm, 0.120mm, 0.130mm, 0.140mm, 0.145mm or 0.150mm. The DOL_0 of the chemically strengthened glass-ceramics is within the above range, indicating that the chemically strengthened glass-ceramics has a high compressive stress layer depth, which is more conducive to offsetting the energy that drives the crack to expand, thereby ensuring that it has excellent damage resistance.
[0193] Meeting specific stress characteristics can ensure that chemically strengthened glass-ceramics has excellent mechanical strength properties, especially excellent drop resistance.
[0194] In some embodiments, the chemically strengthened glass-ceramics with a thickness of 0.6 mm is subjected to multiple fixed-point height drop tests using 120-grit sandpaper, and the fixed-point height of the test is 1.0 m. The number of times the chemically strengthened glass-ceramics is dropped to break is ≥30, preferably ≥50. This indicates that the chemically strengthened glass-ceramics of the present application have excellent anti-drop performance.
[0195] The transparent microcrystalline glass or chemically strengthened microcrystalline glass with excellent optical and mechanical properties provided by the present application can be used for any desired microcrystalline glass device and can be used in many applications. For example, work surfaces, other surfaces, covers of electronic devices or electronic devices, appliance doors, floor tiles, wall panels, storage containers, etc. Other surfaces may include but are not limited to exterior wall surfaces, stair tread surfaces, column veneers, counter surfaces, etc. The types of electronic devices or electronic devices may include but are not limited to handheld, desktop mounted and wall mounted, etc. Covers may include but are not limited to mobile phone covers, mobile phone back panels, tablet computer covers, etc. Storage containers may include but are not limited to plates, beverage bottles, etc. The following detailed description of the embodiments of the present application is exemplary and is only used to explain the present application, and cannot be understood as a limitation on the present application.
[0196] In the example numbers of the following tables, S refers to an embodiment, such as S1 refers to Example 1; D refers to a comparative example, such as D1 refers to Comparative Example 1.
[0197] Example 1
[0198] (1) Preparation of substrate glass: The substrate glass is produced by continuous melting method. The raw materials are prepared according to the ratio of each oxide in S1 of Table 1. After mixing, they are continuously fed into the melting furnace through an automatic feeding device, heated to 1600°C, melted for 24 hours, and then pulled into shape, continuously drawn and cut into required specifications to obtain substrate glass (brick) products. For example, the substrate glass (brick) can be cut into a molding size of 360 mm (length) × 180 mm (width) × 30 mm (thickness).
[0199] Test results of the substrate glass obtained in S1:
[0200] Ⅰ. Through observation, the substrate glass prepared in S1 is overall clear and transparent.
[0201] II. Determine the Tg, heating DSC curve and cooling DSC curve of the substrate glass in S1, record the first exothermic peak temperature T1, the second exothermic peak temperature T2 and their difference data in the heating DSC curve, and calculate the integral area sum S data of the exothermic peak and the endothermic peak contained in the cooling DSC curve within the range of 500℃-900℃, as shown in Table 3, Figure 1 , Figure 3 Table 2 is the calculation result of the relationship between the contents of each oxide in Table 1.
[0202] III. The substrate glass prepared in S1 was heated from room temperature to T at a heating rate of 10°C / min. 1-30 Temperature and T 1-60 temperature, and respectively at T 1-30 Temperature and T 1-60 The treatment was carried out by keeping the temperature at 400 °C for 240 min, and the quartz crystal content in the product obtained after the treatment was tested. The results are shown in Table 3.
[0203] (2) Preparation of microcrystalline glass: Using a heat treatment roller kiln line, the substrate glass is subjected to a heat treatment process to produce microcrystalline glass bricks. The heat treatment process is shown in Table 4, including a nucleation treatment and a crystallization treatment (referred to as heat treatment process B) in sequence. The heating rate of the heat treatment process is 10°C / min. After being taken out of the furnace, microcrystalline glass bricks are obtained.
[0204] Test results of the glass-ceramic bricks obtained from S1:
[0205] Ⅰ. Through observation, the microcrystalline glass bricks obtained in S1 are clear and transparent as a whole.
[0206] II. The crystal phase composition, crystal phase content and crystallinity of the microcrystalline glass were tested, and the results are shown in Table 4. It was calculated that the average crystal size in the microcrystalline glass was 19 nm.
[0207] III. The b values at nine locations on the main surface of the microcrystalline glass with a test size of 360 mm (length) × 180 mm (width) × 30 mm (thickness) are extremely poor. The results are shown in Table 4.
[0208] (3) Cold processing the microcrystalline glass bricks: The above-mentioned microcrystalline glass bricks are cold processed, and the cold processing includes shaping, slicing, CNC processing, grinding, and polishing in sequence to obtain microcrystalline glass sheets with a size of 170 mm (length) × 80 mm (width) × 0.6 mm (thickness).
[0209] Test results of the glass-ceramic sheet obtained from S1:
[0210] Ⅰ. Test the optical properties of the glass-ceramic sheet, including the extreme value of b at nine locations on the main surface of the glass-ceramic sheet, the average value of b at nine locations, haze and transmittance. The test results are shown in Table 4.
[0211] Ⅱ. Test the XRD diffraction curves of the glass-ceramic sheet at the maximum b value position and the minimum b value position in the nine b value tests respectively. The comparison is as follows: Fig.15 As shown. Fig.15 It can be seen that in the microcrystalline glass sheet, the crystal phase structure at the position with the maximum b value and the position with the minimum b value on the main surface is basically the same, or the difference is very small, which indicates that the microcrystalline glass sheet is relatively uniform as a whole, and the optical display effect should be consistent.
[0212] (4) Preparation of chemically strengthened microcrystalline glass: The microcrystalline glass sheet with dimensions of 170 mm (length) × 80 mm (width) × 0.6 mm (thickness) obtained in step (3) was placed in a mixed nitrate salt bath of 70.00 wt% KNO3 + 30.00 wt% NaNO3 + 0.03 wt% LiNO3 (here, based on the total amount of NaNO3 and KNO3 in the mixed molten salt, the mixed molten salt contains 0.03 wt% LiNO3) at 470°C for 7.0 h to obtain chemically strengthened microcrystalline glass, t = 0.6 mm.
[0213] Test results of chemically strengthened glass-ceramics obtained from S1:
[0214] The obtained chemically strengthened microcrystalline glass was subjected to a 1.0 m fixed-point height drop resistance test using 120-grit sandpaper; the surface Na2O concentration, CS_50, |CT_AV|, and DOL_0 of the chemically strengthened microcrystalline glass were tested. The test data are shown in Table 5.
[0215] Example 2-Example 28
[0216] The methods are respectively carried out with reference to Example 1, except that the raw material compositions and the corresponding test results of each example are shown in Tables 1 to 5. The transparent microcrystalline glass of Examples 2 to 28 all meet the following requirements: the appearance is clear and transparent as a whole, without cracking; the crystalline phase of the transparent microcrystalline glass is mainly Li2Si2O5, LiAlSi4O 10 , there is no quartz crystal phase. According to calculation, the average crystal size of the glass-ceramics of Examples 2 to 28 is between 10 and 50 nm.
[0217] The substrate glass of Example 3 is subjected to heat treatment process A (crystallization temperature is T 1-60 The XRD diffraction pattern of the product obtained after Figure 7 As shown, Figure 7 The XRD diffraction pattern of the product obtained after the substrate glass of Example 3 was subjected to heat treatment process A is shown as follows: Fig. 9 The crystal phase is shown in Table 4. The transmittance curve of the microcrystalline glass sheet obtained after the substrate glass of Example 6 is subjected to heat treatment process B when the thickness is 0.6 mm is as shown in Fig.17 The temperature rise DSC curve of the substrate glass of Example 22 is shown as follows: Figure 4 shown.
[0218] Comparative Example 1-Comparative Example 13
[0219] The results are respectively carried out with reference to Example 1, except that the raw material compositions of each comparative example and the corresponding test results are shown in Tables 6 to 11. The heating DSC curve of the substrate glass of Comparative Example 1 is shown in Figure 5 The heating DSC curve of the substrate glass of Comparative Example 2 is shown as Figure 6 As shown, the substrate glass of Comparative Example 2 is subjected to heat treatment process A (crystallization temperature is T 1-60 The XRD diffraction pattern of the product obtained after Figure 8 As shown, the XRD diffraction pattern of the product obtained after the substrate glass of Comparative Example 2 was subjected to heat treatment process B is as follows Fig.10 The crystal phase is shown in Table 9. The cooling DSC curve of the substrate glass of Comparative Example 4 is shown in Figure 2 As shown, the transmittance curve of the glass-ceramic sheet obtained after the substrate glass of Comparative Example 4 is subjected to heat treatment process B is as follows when the thickness is 0.6 mm. Fig.18 shown.
[0220] In the nine b-value tests of the microcrystalline glass sheet (with flower pieces) of Comparative Example 6, the XRD diffraction curves at the maximum b-value position and the minimum b-value position are compared. Fig.16As shown in the figure, it can be seen that there is a clear difference in the crystal phase structure at the maximum b value position and the minimum b value position of the main surface of the microcrystalline glass sheet, which indicates that the overall structure of the microcrystalline glass sheet is quite different, which will lead to differences in the overall display effect, resulting in local color development and / or overall color unevenness on the main surface. The molten appearance of the substrate glass of Comparative Example 9 is milky white, such as Fig.19 After the substrate glass brick of comparative example 7 was treated by heat treatment process B, the microcrystalline glass brick cracked, as shown in FIG. Fig. 20 As shown, in Fig. 20 Obvious cracks can be seen in the square frame. According to calculation, the average crystal size of the microcrystalline glass of Comparative Examples 1 to 12 is greater than 20 nm.
[0221] Table 1
[0222] Composition (mol%) <![CDATA[SiO2]]> <![CDATA[Al2O3]]> <![CDATA[P2O5]]> <![CDATA[ZrO2]]> <![CDATA[Na2O]]> <![CDATA[K2O]]> <![CDATA[Li2O]]> CaO <![CDATA[B2O3]]> S1 69.29 4.11 1.01 2.64 0.29 0.08 21.49 0.79 0.30 S2 70.36 4.17 1.03 2.68 0.30 0.08 20.28 0.80 0.30 S3 70.00 4.15 1.02 2.66 0.29 0.09 20.68 0.80 0.31 S4 69.64 4.13 1.02 2.65 0.29 0.08 21.09 0.80 0.30 S5 68.59 4.07 1.00 2.61 0.29 0.08 22.27 0.79 0.30 S6 67.91 4.03 0.99 2.58 0.29 0.08 23.04 0.78 0.30 S7 69.36 4.11 0.91 2.64 0.29 0.08 21.51 0.79 0.31 S8 69.22 4.10 1.11 2.63 0.29 0.08 21.47 0.79 0.31 S9 69.49 4.12 1.02 2.64 0.00 0.08 21.55 0.80 0.30 S10 69.07 4.09 1.01 2.63 0.61 0.08 21.42 0.79 0.30 S11 68.79 4.08 1.01 2.63 1.00 0.08 21.33 0.79 0.29 S12 69.50 4.12 1.02 2.64 0.29 0.08 21.55 0.80 0.00 S13 69.23 4.10 1.01 2.63 0.29 0.08 21.47 0.79 0.40 S14 69.08 4.09 1.01 2.63 0.29 0.08 21.42 0.79 0.61 S15 68.87 4.08 1.01 2.62 0.29 0.08 21.36 0.79 0.90 S16 69.36 3.71 1.02 2.64 0.29 0.08 21.81 0.79 0.30 S17 69.15 4.30 1.01 2.63 0.29 0.08 21.44 0.79 0.31 S18 68.94 4.59 1.01 2.62 0.29 0.08 21.38 0.79 0.30 S19 69.15 4.10 1.01 2.83 0.29 0.08 21.44 0.80 0.30 S20 69.01 4.09 1.01 3.03 0.29 0.08 21.40 0.79 0.30 S21 68.80 4.08 1.01 3.32 0.29 0.08 21.34 0.79 0.29 S22 69.01 4.09 0.91 2.62 0.29 0.08 21.91 0.79 0.30 S23 68.25 4.05 1.20 2.60 0.29 0.08 22.46 0.78 0.29 S24 69.29 4.01 0.91 2.84 0.29 0.08 21.49 0.79 0.30 S25 69.08 3.99 0.91 2.83 0.59 0.08 21.42 0.79 0.31 S26 69.18 4.00 0.86 2.83 0.49 0.08 21.45 0.79 0.32 S27 69.17 4.10 1.01 2.63 0.29 0.08 21.47 0.95 0.30 S28 68.79 4.08 1.01 2.62 0.29 0.08 21.33 1.51 0.29
[0223] Table 2
[0224]
[0225]
[0226] Table 3
[0227]
[0228]
[0229]
[0230]
[0231]
[0232]
[0233]
[0234] Table 6
[0235] Composition (mol%) <![CDATA[SiO2]]> <![CDATA[Al2O3]]> <![CDATA[P2O5]]> <![CDATA[ZrO2]]> <![CDATA[Na2O]]> <![CDATA[K2O]]> <![CDATA[Li2O]]> CaO <![CDATA[B2O3 <!-- 31 -->]]> D1 71.46 4.24 1.05 2.72 0.30 0.08 19.03 0.82 0.30 D2 66.73 3.80 0.92 2.50 0.20 0.08 25.00 0.77 0.00 D3 69.43 4.13 0.80 2.64 0.29 0.08 21.53 0.80 0.30 D4 68.94 4.09 1.80 2.62 0.29 0.08 21.09 0.79 0.30 D5 68.43 4.06 1.00 2.60 0.29 0.08 21.22 0.78 1.54 D6 68.66 4.07 1.01 3.60 0.20 0.08 21.29 0.79 0.30 D7 69.77 4.22 1.24 2.71 0.32 0.08 20.47 0.83 0.36 D8 68.65 4.07 1.01 2.61 0.29 0.99 21.29 0.79 0.30 D9 68.90 4.15 1.00 2.60 0.25 0.10 21.00 1.80 0.20 D10 68.76 4.06 2.00 2.58 0.29 0.08 21.19 0.78 0.26 D11 70.10 4.27 0.83 1.75 1.48 0.00 21.42 0.00 0.15 D12 71.00 4.00 1.00 2.00 0.00 0.00 22.00 0.00 0.00 D13 69.11 5.00 1.00 2.45 0.29 0.08 21.17 0.6 0.30
[0236] Table 7
[0237]
[0238] Table 8
[0239]
[0240] Table 9
[0241]
[0242]
[0243] Table 10
[0244]
[0245] Table 11
[0246]
[0247]
[0248] It can be seen from the above examples in Tables 1 to 5 and the comparative examples in Tables 6 to 11 that, relative to the comparative examples, the embodiment scheme of the present application not only satisfies the content range of each oxide, but also satisfies the composition characteristics of: 18.200≤Li2O / P2O5≤25.500; 14.000≤2×Li2O / (0.5×ZrO2+CaO)≤23.000, and the obtained large-size substrate glass brick has a clear and transparent appearance. The substrate glass has at least two exothermic peaks at a suitable temperature in the heating DSC curve tested by synchronous thermal analysis, and the sum of the integral areas of the exothermic peak and the endothermic peak in the cooling DSC curve is S≤10. The microcrystalline glass bricks obtained by heat treatment of the substrate glass bricks are all transparent and clear in appearance, and there is no cracking in the microcrystalline glass bricks. The obtained microcrystalline glass crystal phase does not contain quartz crystal phase, and the range of the nine b values on the main surface of the microcrystalline glass is low. By adopting the embodiment scheme of the present application, large-sized, uniform microcrystalline glass bricks with excellent optical properties can be mass-produced, and chemically strengthened microcrystalline glass with excellent optical properties, high CS_50, |CT_AV|, DOL_0, and excellent drop resistance can be prepared.
[0249] In the schemes of Comparative Examples 1 to 8, the formula of the substrate glass does not simultaneously meet the following requirements: the content range of each oxide in the present application, as well as 18.200≤Li2O / P2O5≤25.500; 14.000≤2×Li2O / (0.5×ZrO2+CaO)≤23.000. After heat treatment to prepare large-sized microcrystalline glass bricks, the optical properties deteriorate (mainly manifested in large differences in b-values in different regions and undesirable colors of the glass bricks) or the bricks are prone to cracking. In the schemes of Comparative Examples 9 and 10, after preparing large-sized substrate glass bricks, milky white precipitates directly appeared in the substrate glass bricks, the optical properties deteriorated, and the transmittance decreased. In the schemes of Comparative Examples 11 and 12, the mass-produced microcrystalline glass cannot achieve the required excellent mechanical properties after chemical strengthening treatment, and the anti-drop effect is worse than that of the product of the present application. In the scheme of Comparative Example 13, milky white precipitates and undissolved matter appeared in the prepared large-sized substrate glass bricks.
[0250] The preferred embodiments of the present application are described in detail above; however, the present application is not limited thereto.
Claims
1. A transparent microcrystalline glass, characterized in that: The transparent glass-ceramics contains a petalite crystalline phase and a lithium disilicate crystalline phase, wherein the petalite crystalline phase and the lithium disilicate crystalline phase have a higher weight percentage than other crystalline phases present in the transparent glass-ceramics; Measured in terms of molar percentage of oxides, the composition of the transparent glass-ceramics includes: SiO2: 60.90mol%-72.65mol%, Al2O3: 1.50mol%-5.00mol%, P2O5: 0.85mol%-1.50mol%, ZrO2: 2.00mol%-4.00mol%, Na2O: 0.00mol%-1.00mol%, K2O: 0.00mol%-0.50mol%, Li2O: 20.00mol%-30.00mol%, CaO: 0.00mol%-1.60mol%, B2O3: 0.00mol%-1.00mol%; The composition of the transparent glass-ceramics satisfies the following requirements, measured by the content of each oxide in the transparent glass-ceramics as expressed by molar percentage: 18.200≤Li2O / P2O5≤25.500; 4.100≤(Li2O+Na2O+K2O+B2O3) / (P2O5+ZrO2+CaO)≤6.000; 14.000≤2×Li2O / (0.5×ZrO2+CaO)≤23.
000.
2. The transparent microcrystalline glass according to claim 1, characterized in that: The composition of the transparent microcrystalline glass satisfies the following conditions: 0.100≤P2O5×(CaO+ZrO2+Li2O+Al2O3) / (Na2O+K2O+B2O3)≤0.900, measured by the content of each oxide in the transparent microcrystalline glass as a molar percentage.
3. The transparent microcrystalline glass according to claim 2, characterized in that: 0.190≤P2O5×(CaO+ZrO2+Li2O+Al2O3) / (Na2O+K2O+B2O3)≤0.
900.
4. The transparent microcrystalline glass according to claim 1, characterized in that: Measured in terms of molar percentage of oxides, the composition of the transparent glass-ceramics includes: SiO2: 67.50mol%-71.00mol%, Al2O3: 3.50mol%-5.00mol%, P2O5: 0.85mol%-1.50mol%, ZrO2: 2.50mol%-3.50mol%, Na2O: 0.00mol%-1.00mol%, K2O: greater than 0.00mol% and not more than 0.50mol%, Li2O: 20.00mol%-25.00mol%, CaO: greater than 0.50mol% and not more than 1.60mol%, B2O3: 0.00mol%-1.00mol%.
5. The transparent microcrystalline glass according to claim 2, characterized in that: Measured in terms of molar percentage of oxides, the composition of the transparent glass-ceramics includes: SiO2: 67.50mol%-71.00mol%, Al2O3: 3.50mol%-5.00mol%, P2O5: 0.85mol%-1.50mol%, ZrO2: 2.50mol%-3.50mol%, Na2O: 0.00mol%-1.00mol%, K2O: greater than 0.00mol% and not more than 0.50mol%, Li2O: 20.00mol%-25.00mol%, CaO: greater than 0.50mol% and not more than 1.60mol%, B2O3: 0.00mol%-1.00mol%.
6. The transparent microcrystalline glass according to any one of claims 1 to 5, characterized in that: The transparent microcrystalline glass does not contain a quartz crystal phase.
7. The transparent microcrystalline glass according to any one of claims 1 to 5, characterized in that: The crystallinity of the transparent microcrystalline glass is ≥70.00 wt %; in the transparent microcrystalline glass, the average crystal size does not exceed 100 nm.
8. The transparent microcrystalline glass according to claim 7, characterized in that: The crystallinity of the transparent glass-ceramics is ≥80.00 wt %.
9. The transparent microcrystalline glass according to claim 6, characterized in that: The crystallinity of the transparent microcrystalline glass is ≥70.00 wt %; in the transparent microcrystalline glass, the average crystal size does not exceed 100 nm.
10. The transparent microcrystalline glass according to any one of claims 1 to 5, characterized in that: In the transparent glass-ceramics, the petalite crystal phase accounts for 35.00 wt %-50.00 wt % of the mass of the transparent glass-ceramics, and the lithium disilicate crystal phase accounts for 35.00 wt %-50.00 wt % of the mass of the transparent glass-ceramics.
11. The transparent microcrystalline glass according to claim 6, characterized in that: In the transparent glass-ceramics, the petalite crystal phase accounts for 35.00 wt %-50.00 wt % of the mass of the transparent glass-ceramics, and the lithium disilicate crystal phase accounts for 35.00 wt %-50.00 wt % of the mass of the transparent glass-ceramics.
12. The transparent glass-ceramics according to claim 7, characterized in that: In the transparent glass-ceramics, the petalite crystal phase accounts for 35.00 wt %-50.00 wt % of the mass of the transparent glass-ceramics, and the lithium disilicate crystal phase accounts for 35.00 wt %-50.00 wt % of the mass of the transparent glass-ceramics.
13. The transparent microcrystalline glass according to any one of claims 1 to 5, characterized in that: The transparent microcrystalline glass also contains one or more of a lithium silicate crystal phase, a lithium phosphate crystal phase, and a spodumene crystal phase as a secondary crystalline phase.
14. The transparent microcrystalline glass according to claim 6, characterized in that: The transparent microcrystalline glass also contains one or more of a lithium silicate crystal phase, a lithium phosphate crystal phase, and a spodumene crystal phase as a secondary crystalline phase.
15. The transparent glass-ceramics according to claim 7, characterized in that: The transparent microcrystalline glass also contains one or more of a lithium silicate crystal phase, a lithium phosphate crystal phase, and a spodumene crystal phase as a secondary crystalline phase.
16. The transparent microcrystalline glass according to claim 10, characterized in that: The transparent microcrystalline glass also contains one or more of a lithium silicate crystal phase, a lithium phosphate crystal phase, and a spodumene crystal phase as a secondary crystalline phase.
17. The transparent glass-ceramics according to claim 13, characterized in that: In the transparent microcrystalline glass, the secondary crystalline phase accounts for less than 30.00wt% of the mass of the transparent microcrystalline glass.
18. The transparent glass-ceramics according to claim 14, characterized in that: In the transparent microcrystalline glass, the secondary crystalline phase accounts for less than 30.00wt% of the mass of the transparent microcrystalline glass.
19. The transparent glass-ceramics according to claim 15, characterized in that: In the transparent microcrystalline glass, the secondary crystalline phase accounts for less than 30.00wt% of the mass of the transparent microcrystalline glass.
20. The transparent microcrystalline glass according to claim 16, characterized in that: In the transparent microcrystalline glass, the secondary crystalline phase accounts for less than 30.00wt% of the mass of the transparent microcrystalline glass.
21. The transparent microcrystalline glass according to claim 17, characterized in that: In the transparent microcrystalline glass, the secondary crystalline phase accounts for less than 10.00wt% of the mass of the transparent microcrystalline glass.
22. The transparent glass-ceramics according to any one of claims 1 to 5, characterized in that: When the length, width and thickness specifications of the transparent microcrystalline glass are (200 mm-500 mm)×(100 mm-500 mm)×(10 mm-40 mm), the range of the b values at nine locations on the main surface of the transparent microcrystalline glass is ≤2.00; The nine positions are as follows: (1) four test positions of the test circle I that is tangent to the long side and the adjacent short side on the main surface; (2) four test positions of the test circle II formed by the point on the line segment formed by the centers of the four test circles I that is closest to the middle of the long side or the short side of the main surface; (3) one test circle III formed by the center point of the main surface.
23. The transparent microcrystalline glass according to claim 6, characterized in that: When the length, width and thickness specifications of the transparent microcrystalline glass are (200 mm-500 mm)×(100 mm-500 mm)×(10 mm-40 mm), the range of the b values at nine locations on the main surface of the transparent microcrystalline glass is ≤2.00; The nine positions are as follows: (1) four test positions of the test circle I that is tangent to the long side and the adjacent short side on the main surface; (2) four test positions of the test circle II formed by the point on the line segment formed by the centers of the four test circles I that is closest to the middle of the long side or the short side of the main surface; (3) one test circle III formed by the center point of the main surface.
24. The transparent glass-ceramics according to claim 7, characterized in that: When the length, width and thickness specifications of the transparent microcrystalline glass are (200 mm-500 mm)×(100 mm-500 mm)×(10 mm-40 mm), the range of the b values at nine locations on the main surface of the transparent microcrystalline glass is ≤2.00; The nine positions are as follows: (1) four test positions of the test circle I that is tangent to the long side and the adjacent short side on the main surface; (2) four test positions of the test circle II formed by the point on the line segment formed by the centers of the four test circles I that is closest to the middle of the long side or the short side of the main surface; (3) one test circle III formed by the center point of the main surface.
25. The transparent glass-ceramics according to claim 10, characterized in that: When the length, width and thickness specifications of the transparent microcrystalline glass are (200 mm-500 mm)×(100 mm-500 mm)×(10 mm-40 mm), the range of the b values at nine locations on the main surface of the transparent microcrystalline glass is ≤2.00; The nine positions are as follows: (1) four test positions of the test circle I that is tangent to the long side and the adjacent short side on the main surface; (2) four test positions of the test circle II formed by the point on the line segment formed by the centers of the four test circles I that is closest to the middle of the long side or the short side of the main surface; (3) one test circle III formed by the center point of the main surface.
26. The transparent glass-ceramics according to claim 13, characterized in that: When the length, width and thickness specifications of the transparent microcrystalline glass are (200 mm-500 mm)×(100 mm-500 mm)×(10 mm-40 mm), the range of the b values at nine locations on the main surface of the transparent microcrystalline glass is ≤2.00; The nine positions are as follows: (1) four test positions of the test circle I that is tangent to the long side and the adjacent short side on the main surface; (2) four test positions of the test circle II formed by the point on the line segment formed by the centers of the four test circles I that is closest to the middle of the long side or the short side of the main surface; (3) one test circle III formed by the center point of the main surface.
27. The transparent glass-ceramics according to claim 17, characterized in that: When the length, width and thickness specifications of the transparent microcrystalline glass are (200 mm-500 mm)×(100 mm-500 mm)×(10 mm-40 mm), the range of the b values at nine locations on the main surface of the transparent microcrystalline glass is ≤2.00; The nine positions are as follows: (1) four test positions of the test circle I that is tangent to the long side and the adjacent short side on the main surface; (2) four test positions of the test circle II formed by the point on the line segment formed by the centers of the four test circles I that is closest to the middle of the long side or the short side of the main surface; (3) one test circle III formed by the center point of the main surface.
28. The transparent microcrystalline glass according to claim 22, characterized in that: When the length, width and thickness specifications of the transparent microcrystalline glass are (200 mm-500 mm)×(100 mm-500 mm)×(10 mm-40 mm), the range of the b values at nine locations on the main surface of the transparent microcrystalline glass is ≤1.
50.
29. The transparent microcrystalline glass according to claim 28, characterized in that: When the length, width and thickness specifications of the transparent microcrystalline glass are (200 mm-500 mm)×(100 mm-500 mm)×(10 mm-40 mm), the range of the b values at nine locations on the main surface of the transparent microcrystalline glass is ≤1.
00.
30. The transparent glass-ceramics according to any one of claims 1 to 5, characterized in that: When the length, width and thickness specifications of the transparent microcrystalline glass are (45mm-450mm)×(45mm-350mm)×(0.4mm-2.0mm), the range of the b values at nine locations on the main surface of the transparent microcrystalline glass is ≤0.30; The nine positions are as follows: (1) four test positions of the test circle I that is tangent to the long side and the adjacent short side on the main surface; (2) four test positions of the test circle II formed by the point on the line segment formed by the centers of the four test circles I that is closest to the middle of the long side or the short side of the main surface; (3) one test circle III formed by the center point of the main surface.
31. The transparent glass-ceramics according to claim 6, characterized in that: When the length, width and thickness specifications of the transparent microcrystalline glass are (45mm-450mm)×(45mm-350mm)×(0.4mm-2.0mm), the range of the b values at nine locations on the main surface of the transparent microcrystalline glass is ≤0.30; The nine positions are as follows: (1) four test positions of the test circle I that is tangent to the long side and the adjacent short side on the main surface; (2) four test positions of the test circle II formed by the point on the line segment formed by the centers of the four test circles I that is closest to the middle of the long side or the short side of the main surface; (3) one test circle III formed by the center point of the main surface.
32. The transparent microcrystalline glass according to claim 7, characterized in that: When the length, width and thickness specifications of the transparent microcrystalline glass are (45mm-450mm)×(45mm-350mm)×(0.4mm-2.0mm), the range of the b values at nine locations on the main surface of the transparent microcrystalline glass is ≤0.30; The nine positions are as follows: (1) four test positions of the test circle I that is tangent to the long side and the adjacent short side on the main surface; (2) four test positions of the test circle II formed by the point on the line segment formed by the centers of the four test circles I that is closest to the middle of the long side or the short side of the main surface; (3) one test circle III formed by the center point of the main surface.
33. The transparent microcrystalline glass according to claim 10, characterized in that: When the length, width and thickness specifications of the transparent microcrystalline glass are (45mm-450mm)×(45mm-350mm)×(0.4mm-2.0mm), the range of the b values at nine locations on the main surface of the transparent microcrystalline glass is ≤0.30; The nine positions are as follows: (1) four test positions of the test circle I that is tangent to the long side and the adjacent short side on the main surface; (2) four test positions of the test circle II formed by the point on the line segment formed by the centers of the four test circles I that is closest to the middle of the long side or the short side of the main surface; (3) one test circle III formed by the center point of the main surface.
34. The transparent glass-ceramics according to claim 13, characterized in that: When the length, width and thickness specifications of the transparent microcrystalline glass are (45mm-450mm)×(45mm-350mm)×(0.4mm-2.0mm), the range of the b values at nine locations on the main surface of the transparent microcrystalline glass is ≤0.30; The nine positions are as follows: (1) four test positions of the test circle I that is tangent to the long side and the adjacent short side on the main surface; (2) four test positions of the test circle II formed by the point on the line segment formed by the centers of the four test circles I that is closest to the middle of the long side or the short side of the main surface; (3) one test circle III formed by the center point of the main surface.
35. The transparent glass-ceramics according to claim 17, characterized in that: When the length, width and thickness specifications of the transparent microcrystalline glass are (45mm-450mm)×(45mm-350mm)×(0.4mm-2.0mm), the range of the b values at nine locations on the main surface of the transparent microcrystalline glass is ≤0.30; The nine positions are as follows: (1) four test positions of the test circle I that is tangent to the long side and the adjacent short side on the main surface; (2) four test positions of the test circle II formed by the point on the line segment formed by the centers of the four test circles I that is closest to the middle of the long side or the short side of the main surface; (3) one test circle III formed by the center point of the main surface.
36. The transparent microcrystalline glass according to claim 30, characterized in that: When the length, width and thickness specifications of the transparent microcrystalline glass are (45mm-450mm)×(45mm-350mm)×(0.4mm-2.0mm), the extreme difference of the b values at nine locations on the main surface of the transparent microcrystalline glass is ≤0.
10.
37. The transparent microcrystalline glass according to claim 30, characterized in that: When the length, width and thickness specifications of the transparent microcrystalline glass are (45mm-450mm)×(45mm-350mm)×(0.4mm-2.0mm), the extreme difference of the b values at nine locations on the main surface of the transparent microcrystalline glass is ≤0.
06.
38. The transparent glass-ceramics according to any one of claims 1 to 5, characterized in that: When the thickness of the transparent microcrystalline glass is 0.6 mm, the b value is ≤1.00, the haze is ≤0.25%, and the transmittance of the transparent microcrystalline glass is ≥90.00% under light of a wavelength of 550 nm.
39. The transparent glass-ceramics according to claim 6, characterized in that: When the thickness of the transparent microcrystalline glass is 0.6 mm, the b value is ≤1.00, the haze is ≤0.25%, and the transmittance of the transparent microcrystalline glass is ≥90.00% under light of a wavelength of 550 nm.
40. The transparent microcrystalline glass according to claim 7, characterized in that: When the thickness of the transparent microcrystalline glass is 0.6 mm, the b value is ≤1.00, the haze is ≤0.25%, and the transmittance of the transparent microcrystalline glass is ≥90.00% under light of a wavelength of 550 nm.
41. The transparent glass-ceramics according to claim 10, characterized in that: When the thickness of the transparent microcrystalline glass is 0.6 mm, the b value is ≤1.00, the haze is ≤0.25%, and the transmittance of the transparent microcrystalline glass is ≥90.00% under light of a wavelength of 550 nm.
42. The transparent microcrystalline glass according to claim 13, characterized in that: When the thickness of the transparent microcrystalline glass is 0.6 mm, the b value is ≤1.00, the haze is ≤0.25%, and the transmittance of the transparent microcrystalline glass is ≥90.00% under light of a wavelength of 550 nm.
43. The transparent glass-ceramics according to claim 17, characterized in that: When the thickness of the transparent microcrystalline glass is 0.6 mm, the b value is ≤1.00, the haze is ≤0.25%, and the transmittance of the transparent microcrystalline glass is ≥90.00% under light of a wavelength of 550 nm.
44. The transparent glass-ceramics according to claim 22, characterized in that: When the thickness of the transparent microcrystalline glass is 0.6 mm, the b value is ≤1.00, the haze is ≤0.25%, and the transmittance of the transparent microcrystalline glass is ≥90.00% under light of a wavelength of 550 nm.
45. The transparent glass-ceramics according to claim 30, characterized in that: When the thickness of the transparent microcrystalline glass is 0.6 mm, the b value is ≤1.00, the haze is ≤0.25%, and the transmittance of the transparent microcrystalline glass is ≥90.00% under light of a wavelength of 550 nm.
46. The transparent microcrystalline glass according to claim 38, characterized in that: When the thickness of the transparent microcrystalline glass is 0.6 mm, the b value is ≤0.70 and the haze is ≤0.18%.
47. The transparent glass-ceramics according to claim 38, characterized in that: When the thickness of the transparent microcrystalline glass is 0.6 mm, the b value is ≤0.60, the haze is ≤0.16%, and the transmittance of the transparent microcrystalline glass is ≥90.50% under light of a wavelength of 550 nm.
48. A substrate glass, which can be used to prepare the transparent microcrystalline glass as claimed in claim 1 after heat treatment, characterized in that: The composition of the substrate glass includes, in terms of molar percentage of oxides: SiO2: 60.90mol%-72.65mol%, Al2O3: 1.50mol%-5.00mol%, P2O5: 0.85mol%-1.50mol%, ZrO2: 2.00mol%-4.00mol%, Na2O: 0.00m ol%-1.00mol%, K2O: 0.00mol%-0.50mol%, Li2O: 20.00mol%-30.00mol%, CaO: 0.00mol%-1.60mol%, B2O3: 0.00mol%-1.00mol%; The composition of the substrate glass satisfies the following conditions, expressed in terms of the molar percentage of each oxide in the substrate glass composition: 18.200≤Li2O / P2O5≤25.500; 4.100≤(Li2O+Na2O+K2O+B2O3) / (P2O5+ZrO2+CaO)≤6.000; 14.000≤2×Li2O / (0.5×ZrO2+CaO)≤23.
000.
49. The substrate glass according to claim 48, characterized in that The composition of the substrate glass satisfies the following conditions, expressed in terms of the molar percentage of each oxide in the substrate glass composition: 0.100≤P2O5×(CaO+ZrO2+Li2O+Al2O3) / (Na2O+K2O+B2O3)≤0.
900.
50. The substrate glass according to claim 49, characterized in that 0.190≤P2O5×(CaO+ZrO2+Li2O+Al2O3) / (Na2O+K2O+B2O3)≤0.
900.
51. The substrate glass according to claim 48, characterized in that According to the synchronous thermal analysis test, under the protective atmosphere of nitrogen, the substrate glass is heated from room temperature to 900°C at a heating rate of 10°C / min to obtain a heating DSC curve. In the heating DSC curve, there are at least two exothermic peaks, wherein the first exothermic peak temperature T1 is 600°C-730°C, and the second exothermic peak temperature T2 is 740°C-800°C, and T1 and T2 satisfy the relationship: 100°C ≥ T2-T1 ≥ 40°C.
52. The substrate glass according to claim 49, characterized in that According to the synchronous thermal analysis test, under the protective atmosphere of nitrogen, the substrate glass is heated from room temperature to 900°C at a heating rate of 10°C / min to obtain a heating DSC curve. In the heating DSC curve, there are at least two exothermic peaks, wherein the first exothermic peak temperature T1 is 600°C-730°C, and the second exothermic peak temperature T2 is 740°C-800°C, and T1 and T2 satisfy the relationship: 100°C ≥ T2-T1 ≥ 40°C.
53. The substrate glass according to claim 51, characterized in that 80℃≥T2-T1≥50℃.
54. The substrate glass according to any one of claims 48 to 52, characterized in that According to the synchronous thermal analysis test, the substrate glass was heated from room temperature to 1400°C for 10 minutes at a heating rate of 10°C / min under a nitrogen protective atmosphere, and then cooled from 1400°C to 450°C at a cooling rate of 10°C / min, to obtain a cooling DSC curve. In the cooling DSC curve, within the range of 500°C-900°C, the sum of the integrated areas of the exothermic peak and the endothermic peak contained therein is S≤10.
55. The substrate glass according to claim 53, characterized in that In the cooling DSC curve, there is no endothermic peak and / or exothermic peak in the range of 500°C-900°C.
56. The substrate glass according to claim 54, characterized in that In the cooling DSC curve, S=0 in the range of 500℃-900℃.
57. The substrate glass according to any one of claims 48 to 52, characterized in that The substrate glass was heated from room temperature to T at a heating rate of 10°C / min. 1-30 The treated product has a quartz crystal content of less than 15 wt %, wherein T 1-30 =T1-30℃; and / or, The substrate glass was heated from room temperature to T at a heating rate of 10°C / min. 1-60 temperature, and kept at this temperature for 240 minutes for treatment, and the content of quartz crystal phase in the product obtained after treatment is less than 5wt%, wherein T 1-60 =T1-60℃.
58. The substrate glass according to claim 53, characterized in that The substrate glass was heated from room temperature to T at a heating rate of 10°C / min. 1-30 The treated product has a quartz crystal content of less than 15 wt %, wherein T 1-30 =T1-30℃; and / or, The substrate glass was heated from room temperature to T at a heating rate of 10°C / min. 1-60 temperature, and kept at this temperature for 240 minutes for treatment, and the content of quartz crystal phase in the product obtained after treatment is less than 5wt%, wherein T 1-60 =T1-60℃.
59. The substrate glass according to claim 57, characterized in that The substrate glass was heated from room temperature to T at a heating rate of 10°C / min. 1-60 temperature, and kept at this temperature for 240 minutes for treatment. After treatment, the product obtained has no quartz crystal phase, wherein T 1-60 =T1-60℃.
60. A chemically strengthened glass-ceramic, characterized in that: The composition at the center of the chemically strengthened glass-ceramics is the same as the composition of the transparent glass-ceramics described in claim 1, and the chemically strengthened glass-ceramics includes a compressive stress layer region extending from the surface of the transparent glass-ceramics to the compression depth, and has tensile stress inside the chemically strengthened glass-ceramics.
61. The chemically strengthened glass-ceramics according to claim 60, characterized in that: The chemically strengthened microcrystalline glass is obtained by subjecting the transparent microcrystalline glass described in claim 1 to chemical strengthening treatment, wherein the salt bath used for chemical strengthening treatment is a mixed molten salt, and the composition of the mixed molten salt includes: 0<NaNO3<100wt%, 0<KNO3<100wt%, 0<LiNO3≤0.2wt%; the temperature of the salt bath used for chemical strengthening treatment is 430℃-530℃, and the time of the chemical strengthening treatment is 0.5h-15.0h.
62. The chemically strengthened glass-ceramics according to claim 60, characterized in that: The surface Na2O concentration of the chemically strengthened glass-ceramics is 5.0wt%-20.0wt%.
63. The chemically strengthened glass-ceramics according to any one of claims 60 to 62, characterized in that: The chemically strengthened glass-ceramics has a CS_50 of 110-200 MPa, where CS_50 refers to a compressive stress value at a depth of 50 μm from the main surface of the chemically strengthened glass-ceramics; and / or, The chemically strengthened glass-ceramics has a |CT_AV| of 84-140 MPa, where |CT_AV| refers to the absolute value of the average tensile stress.
64. The chemically strengthened glass-ceramics according to any one of claims 60 to 62, characterized in that: The depth DOL_0 of the compressive stress layer of the chemically strengthened glass-ceramics is 0.18t-0.25t, where t is the thickness of the chemically strengthened glass-ceramics.
65. The chemically strengthened glass-ceramics according to claim 63, characterized in that: The depth DOL_0 of the compressive stress layer of the chemically strengthened glass-ceramics is 0.18t-0.25t, where t is the thickness of the chemically strengthened glass-ceramics.
66. The chemically strengthened glass-ceramics according to any one of claims 60 to 62, characterized in that: The chemically strengthened microcrystalline glass having a thickness of 0.6 mm was subjected to multiple fixed-point height drop tests using 120-grit sandpaper. The fixed-point height of the test was 1.0 m. The number of times the chemically strengthened microcrystalline glass was dropped and broken was ≥30.
67. The chemically strengthened glass-ceramics according to claim 63, characterized in that: The chemically strengthened microcrystalline glass having a thickness of 0.6 mm was subjected to multiple fixed-point height drop tests using 120-grit sandpaper. The fixed-point height of the test was 1.0 m. The number of times the chemically strengthened microcrystalline glass was dropped and broken was ≥30.
68. The chemically strengthened glass-ceramics according to claim 64, characterized in that: The chemically strengthened microcrystalline glass having a thickness of 0.6 mm was subjected to multiple fixed-point height drop tests using 120-grit sandpaper. The fixed-point height of the test was 1.0 m. The number of times the chemically strengthened microcrystalline glass was dropped and broken was ≥30.
69. The chemically strengthened glass-ceramics according to claim 66, characterized in that: The chemically strengthened microcrystalline glass having a thickness of 0.6 mm was subjected to multiple fixed-point height drop tests using 120-mesh sandpaper. The fixed-point height of the test was 1.0 m. The chemically strengthened microcrystalline glass was dropped and broken ≥50 times.
70. A glass device, characterized in that: The glass device comprises the transparent micro-ceramic glass according to any one of claims 1 to 47 or comprises the chemically strengthened micro-ceramic glass according to any one of claims 60 to 69.
71. An electronic device, characterized in that: The electronic device comprises the transparent micro-ceramic glass according to any one of claims 1 to 47 or comprises the chemically strengthened micro-ceramic glass according to any one of claims 60 to 69.
Citation Information
Patent Citations
Chemically strengthened lithium disilicate-petalite glass-ceramics
CN111867993A
High-transmittance low-haze glass composition, microcrystalline glass and preparation method thereof
CN115772002A